A multi-phase fast transmission layer positive electrode material, a preparation method, application and battery
Patent Information
- Application Number
- CN202611282258.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-24
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2046-08-24
AI Technical Summary
与此同时,现有技术中的前驱体构筑、体相掺杂和表面包覆通常相互独立,难以在同一材料中同时实现多相层状主体、局部低能垒传输结构和稳定表界面的协同构筑
[0211](1)通过非锂碱金属层状前驱体的预构型和拓扑交换,在同一颗粒或晶粒内获得共享过渡金属-氧骨架的多堆垛结构域交生主体,避免将“多相”限定为宏观杂相混合;
Smart Images

Figure CN122800597B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of electrochemical energy storage technology, specifically to a multiphase fast-transport layered cathode material, its preparation method, applications, and batteries. Background Technology
[0002] Layered transition metal oxides are one of the most important cathode material systems in lithium-ion batteries. Representative materials include lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium nickel manganese oxide, and lithium-rich layered oxides. Increasing the charging cut-off voltage or the degree of reversible delithiation of the cathode material can improve energy density, but it also causes problems such as abrupt changes in interlayer spacing, transition metal migration, oxygen framework instability, surface lithification, lattice oxygen release, and electrolyte side reactions.
[0003] On the other hand, consumer electronics, unmanned equipment, power batteries, and high-power energy storage devices place higher demands on rapid charging and discharging capabilities. Conventional O3-type layered materials mainly rely on two-dimensional interlayer diffusion, and lithium concentration gradients easily form within their particles under high current conditions, leading to increased polarization, insufficient capacity release, and localized stress concentration. Therefore, simply increasing the theoretical capacity of the host material without simultaneously optimizing the ion transport channels makes it difficult to simultaneously achieve high capacity and high rate performance.
[0004] Existing layered cathode materials typically involve co-precipitating hydroxide or carbonate precursors with a lithium source followed by prolonged high-temperature sintering. This approach places high demands on equipment, wastewater treatment, raw material uniformity, and process control. Furthermore, high-temperature direct lithiation tends to cause the system to shift towards the thermodynamically stable O3 phase, and is prone to particle sintering, cation mixing, and dopant segregation, which is detrimental to the formation of a fast transport structure composed of multiple oxygen stacking mechanisms.
[0005] Bulk doping and surface coating can improve the stability of layered cathodes. Bulk doping can regulate local coordination and metal-oxygen bond strength, but direct high-temperature solid-phase doping in lithium-based materials is easily limited by diffusion kinetics and solid solubility. Ordinary oxide coatings can isolate the electrolyte, but there are often abrupt changes in lattice and chemical composition between the coating and the host material, and there is still room for improvement in interfacial bonding strength, ion transport continuity, and high-temperature and high-voltage stability. At the same time, in existing technologies, precursor construction, bulk doping, and surface coating are usually independent of each other, making it difficult to simultaneously achieve the synergistic construction of a multiphase layered host, a local low-barrier transport structure, and a stable interface in the same material.
[0006] Therefore, overcoming the shortcomings of existing technologies, such as the reliance on multi-component co-precipitation precursors in the preparation of layered cathode materials, the single bulk stacking structure, the lack of fast lithium-ion transport channels, the disconnect between bulk structure regulation and surface / interface protection, and the difficulty in balancing capacity and stability under high voltage and high rate conditions, are urgent problems and challenges to be solved. Summary of the Invention
[0007] This invention addresses the shortcomings of existing preparation techniques by providing a multiphase fast-transport layered cathode material, its preparation method, applications, and batteries. The multiphase fast-transport layered cathode material prepared by this invention exhibits excellent electrochemical performance, particularly high capacity, high rate capability, high voltage structural stability, and excellent cycle life; moreover, the preparation method is simple and easy to industrialize.
[0008] The multiphase fast transport layered cathode material provided by the present invention generally forms a multi-level nested structure from the inside out, which includes a lithium-based layered oxide host material, a composite oxide reconstructed interface layer and a functional coating layer from the inside out. The lithium-based layered oxide host material includes at least two layered structural domains and is in situ bonded to the lithium-based layered oxide host material; the functional coating layer is located on the outside of the particles and / or particle agglomerates.
[0009] The composite oxide reconstructed interface layer stabilizes the local coordination environment and oxygen framework of the primary particle surface, suppressing or mitigating one or more of the following during charge-discharge processes: lattice instability, oxygen loss, cation migration, adverse phase transitions, and abrupt interface structure changes. It also regulates the structural and chemical environment transition from the lithium-based substrate oxide lattice to the particle surface region. The composite oxide reconstructed interface layer can mitigate one or more differences between the host material and the functional coating layer in crystal structure, elemental composition, local coordination state, chemical bonding state, and interfacial chemical properties, reducing structural and compositional abrupt changes caused by direct contact and improving interlayer bonding stability. For primary particle surfaces not directly contacting the functional coating layer, the composite oxide reconstructed interface layer can still independently stabilize the surface lattice and regulate the structure near grain boundaries.
[0010] The functional coating layer is used to reduce direct contact between the electrolyte and the composite oxide reconstruction interface layer and / or the particle surface, and to inhibit the electrolyte from penetrating from the outer surface of the particles or particle agglomerates into the particle interior through grain boundary openings, pores or cracks, thereby reducing interfacial side reactions and internal grain boundary erosion.
[0011] Through the above-mentioned multi-level nested structure, the composite oxide reconstructed interface layer undertakes the functions of surface lattice stabilization, local structural reconstruction, and interface transition at the primary particle scale, while the functional coating layer undertakes the functions of electrolyte isolation and grain boundary entry protection at the particle or particle agglomeration scale. This ensures that the structural stability of the primary particle surface and the interface protection outside the particle are undertaken by different levels, thereby avoiding functional conflicts caused by a single surface layer simultaneously undertaking the functions of main lattice reconstruction, heterogeneous material interface transition, and external electrolyte isolation.
[0012] The present invention solves the above-mentioned technical problems through the following technical solutions:
[0013] The present invention provides a multiphase fast transport layered cathode material, comprising a lithium-based layered oxide host material, a composite oxide reconstructed interface layer located on the surface of the lithium-based layered oxide host material, and a functional coating layer located on the surface of the composite oxide reconstructed interface layer.
[0014] The lithium-based layered oxide host material includes at least two types of layered structural domains, and each layered structural domain has at least one different feature among the oxygen layer stacking sequence, interlayer translation relationship, cell repeating period, lithium ion coordination environment and local layered lattice orientation.
[0015] The composite oxide reconstructed interface layer includes one or more of the following: electrochemically stable layered structure, spinel structure, rock salt structure, perovskite oxide structure, perovskite-like oxide structure, the aforementioned corresponding low crystallinity structure, and amorphous structure.
[0016] The composite oxide reconstructed interface layer is in situ bonded to the surface of the lithium-based morphological oxide host material through one or more of the following methods: shared oxygen framework, element interdiffusion, local lattice connection, structural gradation and compositional gradient.
[0017] The functional coating layer includes one or more of the following: solid electrolyte materials, compounds containing polyanionic structural units, inorganic glassy materials, amorphous oxides, metal oxides, carbonaceous materials, and heat-treated convertible organic polymer materials.
[0018] In this invention, the multiphase fast-transfer layered cathode material does not require each crystal phase to continuously penetrate the particle, as long as different crystal phases, layer slip regions, stacking fault regions, or phase interfaces can jointly form a Li phase that is more abundant than a single thermodynamically stable O3 phase. + Migration paths, or reducing local diffusion distance, diffusion energy barrier and concentration polarization, belong to the multiphase fast transport structure described in this invention.
[0019] In this invention, the "multiphase" structure in the multiphase fast-transport layered cathode material preferably manifests as a nanoscale intergrowth structure within the same particle or grain, rather than a simple mixture of different macroscopic particles. The "multiphase" includes intergrowth of structural domains formed by different layered structure types and / or intergrowth of structural domains with different local layered lattice orientations within the same layered structure type. This multiphase intergrowth structure, while maintaining the integrity of the main layered framework and particle morphology, can construct a lithium-ion transport network composed of interlayer two-dimensional diffusion channels and structural domain boundary bypasses, and improve structural stability under high-rate and high-voltage conditions by dispersing local stress and buffering interlayer slip.
[0020] In this invention, the lithium-based morphological oxide in the lithium-based morphological oxide host material refers to an oxide with a near-close-packed layer composed of oxygen atoms as the basic framework, lithium-ion layers and metal-oxygen layers containing transition metals and / or main group metals alternating along at least one crystallographic direction, and having interlayer sites or channels for lithium-ion insertion, extraction, or migration. The lithium-based morphological oxide may have O3, O2, P2, T2, O6, and their distorted or derived structures; and may include one or more structural or compositional features selected from interlayer slip, stacking faults, stacking misalignments, cation mixing, oxygen vacancies, oxygen non-stoichiometry, non-lithium alkali metal residues, and doping elements. The composite oxide in the composite oxide reconstructed interface layer refers to an oxide composed of at least two different metal elements and oxygen element, and an oxide material in which at least one oxide structural unit forms a solid solution, symbiotic, cross-generation, gradient distribution or continuous transition structure at the nanoscale; the different metal elements can occupy different lattice sites in the same crystal framework, or can form structural units with different local coordination environments; the composite oxide is not required to form a macroscopic crystal phase that can be independently identified by conventional phase analysis, nor does it include the case of simply physical mixing of different oxide particles without forming a structural continuity region, compositional transition region or interface bonding region between them. In the reconstructed composite oxide interface layer, electrochemical stability is used to define layered structures, spinel structures, rock salt structures, perovskite oxide structures, perovskite-like oxide structures, the aforementioned low-crystallinity structures, and amorphous structures, rather than solely defining layered structures. Electrochemical stability means that, under the target charge-discharge voltage range, test temperature, and cycling conditions, the reconstructed composite oxide interface layer essentially does not participate as a major capacity-contributing phase in continuous lithium-ion insertion or extraction, or in corresponding metal or oxygen redox reactions. Its electrochemical reaction intensity is significantly lower than that of the lithium-based layered oxide host material, and it does not undergo significant irreversible phase transitions, structural collapse, decomposition, dissolution, or detachment from the host material surface due to continuous electrochemical reactions. Electrochemical stability does not preclude limited interfacial charge transfer, local valence state adjustment, trace lithium-ion exchange, surface adsorption, bonding state adjustment, or other local reactions that do not damage the basic structure and interfacial protection function of the reconstructed interface layer. In the composite oxide reconstructed interface layer, the layered structure refers to an oxide structure in which metal-oxygen coordination polyhedra or metal-oxygen structural units are connected along a two-dimensional direction to form sheets, and are periodically or quasi-periodically stacked along a direction substantially perpendicular to the sheets, so that the material exhibits a identifiable structural difference in the intralayer direction and the interlayer direction; a lithium ion layer, a non-lithium alkali metal ion layer, a vacancy layer, or an intermediate layer containing other cations may be provided between adjacent sheets.The layered structure may have the same, similar, or different oxygen layer stacking sequence, cation coordination mode, lattice orientation, and cell repeating period as the lithium-based layered oxide host material, and may contain one or more of local layer slip, stacking faults, cation mixing, lattice distortion, and compositional gradient; however, under the above-mentioned target charge-discharge conditions, it does not undergo continuous electrochemical reactions as the main capacity contributing phase.
[0021] In this invention, the layered structural domain refers to a local region within the same particle or grain, composed of one or more adjacent transition metal-oxygen layers and their corresponding lithium-ion layers, exhibiting relatively consistent layered structural characteristics within a certain spatial range. Adjacent layered structural domains have distinguishable local structural differences and / or transition boundaries, but it is not required that each layered structural domain form a macroscopic crystalline phase that can be independently identified by conventional bulk phase diffraction.
[0022] In this invention, the layered structural domains in the lithium-based layered oxide host material can be distributed in a lamellar, strip, block, periodically alternating, or non-periodic mismatched manner, and their characteristic scale can be from a single or multiple transition metal-oxygen layers to tens of nanometers.
[0023] In this invention, in the layered structural domains of the lithium-based layered oxide host material, adjacent layered structural domains preferably share or continuously inherit the transition metal-oxygen framework. The transition between adjacent layered structural domains can be achieved through one or more of the following: relative translation of adjacent transition metal-oxygen layers along the ab plane, layer tilting, in-plane orientation rotation, and change in the oxygen layer stacking order. The transition boundary between adjacent layered structural domains may be accompanied by one or more of the following: stacking faults, stacking mismatches, twins, dislocations, interlayer spacing expansion, lattice bending, and lattice microstrain, but complete fracture or re-nucleation of the transition metal-oxygen framework is not required. The above structure can serve as a fast channel, stress buffer, interlayer support, or phase transition modulator.
[0024] In this invention, the transition boundaries between the layered structural domains and their adjacent layered structural domains can form continuous or partially connected fast transport regions within the main body; different layered structural domains can form different local lithium-ion migration geometries, different stacking structural domains can provide different lithium-ion occupancy environments, and the expanded interlayer spacing, distorted coordination, and aperiodic stacking at the domain boundaries can form local bypasses connecting adjacent interlayer channels; at the same time, layer slip and micro-strain dispersion regions can be used to buffer anisotropic lattice strain during the charging and discharging process and suppress sudden global phase transitions.
[0025] In this invention, the structural type of the layered structural domain is preferably selected from one or more of O3, O2, T2, O6 and their distorted structures.
[0026] In this invention, the differences in the oxygen layer stacking sequence within the layered structural domain generally refer to the different projection positions of the close-packed oxygen layers in the ab plane, represented by A, B, and C. In different layered structural domains, one or more differences exist in the order of A, B, and C positions along the layered stacking direction, the local stacking order, and the stacking continuity. For example, different oxygen layer arrangements correspond to the formation of O3, O2, T2, O6, and their distorted structures. The differences in interlayer translation relationships generally refer to one or more differences in the relative translation direction, translation distance, and translation vector between adjacent transition metal-oxygen layers, adjacent oxygen layers, or adjacent layered framework units along the ab plane. This includes changes in local slip, dislocation, mismatch, or lattice connection relationships between adjacent layers, without requiring complete breakage or re-nucleation of the transition metal-oxygen framework. The differences in the cell repeating period generally refer to the different minimum number of repeating layers and / or minimum repeating distance required for the restoration of equivalent atomic arrangements along the layered stacking direction in different layered structural domains. This includes the number of repeating cells contained in the minimum structural repeating unit. The number of transition metal-oxygen layers, lithium layers, oxygen layers, and period length along the c-axis may differ in one or more of the following: the cell repeating period may also include local repeating periods formed by local stacking mismatches, periodic alternations, or superstructures; the difference in lithium-ion coordination environment generally refers to the different local oxygen coordination geometry, coordination number, site symmetry, and degree of coordination polyhedral distortion of Li sites in different layered structural domains, including one or more of octahedral coordination, triangular prism coordination, tetrahedral coordination, and their distorted coordination; it may also include one or more differences in oxygen vacancies around Li sites, adjacent transition metal elements, doping elements, residual non-lithium alkali metal elements, and local defect environments; the difference in local layered lattice orientation generally refers to the existence of local orientation rotation within the same particle or grain, relative rotation between adjacent transition metal-oxygen layers, layer tilt, lattice bending, or combinations thereof between different layered structural domains, rather than simple crystal orientation differences caused by random orientation between different macroscopic particles. Different layered structural domains may belong to the same long-range ordered layered phase, such as the O3 phase, but their local layered lattice orientation, interlayer connection relationship or defect distribution are different.
[0027] In this invention, the composite oxide reconstructed interface layer can be an independent coating with a single long-range ordered crystalline phase or a composite reconstructed region formed by the intergrowth of multiple local coordination units.
[0028] In this invention, the local structure of the composite oxide reconstructed interface layer can vary with the ratio of non-lithium alkali metal A to Li on the surface, the metal valence state, and the metal element content.
[0029] In this invention, the composite oxide reconstructed interface layer can be formed spontaneously by the rearrangement of existing elements near the substrate during ion exchange and / or heat treatment, or it can be induced by an externally added interface-controlled element source. For example, when the lithium-based morphological oxide substrate material contains Ti, a Ca source can be added to form a Ca-Ti-O reconstructed interface layer; when the lithium-based morphological oxide substrate material is lithium cobalt oxide, a La source can be added to form a La-Co-O reconstructed interface layer with near-surface Co; when the lithium-based morphological oxide substrate material is a high-nickel ternary material, a La source can be added to form a La-Ni / Co / Mn-O reconstructed interface layer; two or more element sources can also be added simultaneously to adjust the composition, thickness, crystallinity, and structural type of the interface layer.
[0030] In this invention, the composite oxide reconstructed interface layer can, on the one hand, reduce direct contact between the lithium-based crystalline oxide host material and the electrolyte and high-voltage side reactions; on the other hand, it can improve the interfacial bonding strength by coupling with the near-surface elements of the lithium-based crystalline oxide host material, and can utilize defects, vacancies, or lithiated perovskite units to maintain the interface Li. + transmission.
[0031] In this invention, the composite oxide reconstructed interface layer can be one or more of the following: a continuous layer, a discontinuous island layer, a dot-like enrichment region, a grain boundary enrichment layer, or a composition and structure gradient layer that gradually changes from the host to the outer surface.
[0032] In this invention, the composite oxide reconstructed interface layer and the lithium-based crystalline oxide host material preferably form one or more of the following: a structural continuity region, a compositional transition region, and a defect-rich region, rather than forming a mechanical contact interface with a complete abrupt change in composition and structure, generated solely by physical adhesion. This region allows the lithium-ion transport channels within the host material to extend to the particle surface, while simultaneously reducing the interfacial impedance between the conventional independent coating layer and the host material caused by lattice mismatch, elemental abrupt changes, or insufficient mechanical contact.
[0033] In this invention, in the composite oxide reconstructed interface layer, the layered structure refers to a structure in which atomic layers are arranged periodically or quasi-periodically along a specific direction and have interstitial structures that can accommodate lithium ions; the spinel structure refers to an AB2O4 type structure or its defect or doped derivative structure with three-dimensional cation migration channels; the rock salt structure refers to a structure in which anions are nearly densely packed and cations mainly occupy octahedral sites and its defect-derived structures; the low crystallinity structure refers to a structure with only finite lattice fringes or short-range order but low long-range order; and the amorphous structure refers to a structure that lacks long-range periodicity that can be identified by conventional diffraction but may have local coordination units.
[0034] In this invention, the perovskite oxide structure refers to an oxide structure that simultaneously satisfies the following conditions: (1) its basic stoichiometry can be expressed as ABO 3±δ (2) The B-site cation forms a BO6 octahedron with oxygen; (3) The BO6 octahedron is mainly connected continuously along three spatial directions through a co-angular connection, forming a three-dimensional framework with long-range periodicity; (4) The A-site cation mainly occupies the interstitial sites formed by the three-dimensional BO6 octahedron framework. The perovskite oxide structure may contain a small amount of oxygen vacancies, cation vacancies, elemental substitutions, local lattice distortions, or disorder defects that do not change the above-mentioned basic stoichiometric relationship of ABO3 and the three-dimensional co-angular connection framework. Structures that only contain the above-mentioned local defects or substitutions but still meet the above conditions are still classified as perovskite oxide structures and not as perovskite-like oxide structures.
[0035] In this invention, the perovskite-like oxide structure refers to an oxide structure that has perovskite structural characteristics in terms of local coordination mode, basic structural unit, or atomic connection relationship, but does not simultaneously meet all the above-mentioned limiting conditions for perovskite-like oxide structures. The perovskite-like oxide structure has at least one of the following characteristics: (1) its basic stoichiometry deviates significantly from ABO. 3±δ (2) It has two or more ordered B-site cation sublattices; (3) The BO6 octahedron does not form a continuous framework along three spatial directions mainly through the co-angular mechanism; (4) Its perovskite characteristic framework extends only along one or two spatial directions; (5) Its vacancies, cation occupancy or structural units are ordered, thereby forming a cell period or connection framework different from ABO3 type perovskite; (6) It only has local coordination units or short-range ordered regions with perovskite characteristics at the nanoscale, and does not have long-range periodicity that can be attributed to ABO3 type perovskite structure.
[0036] In this invention, the perovskite-like oxide structure preferably includes one or more of the following: defect perovskite, double perovskite, layered perovskite, and interface structure composed of nanoscale short-range ordered perovskite units but with insufficient long-range crystallinity.
[0037] In this invention, the chemical formula of the lithium-based crystalline oxide host material can be represented as Li x A m TM 1-y M y O 2±δ and / or Li x+α A m TM 1-α-y M y O 2±δ Where A is a non-lithium alkali metal, TM is a transition metal and / or main group metal that constitutes the main framework of lithium-based basal oxide materials, and M is a doping element.
[0038] Wherein, the Li x A m TM 1-y M y O 2±δ Preferably, 0.2 ≤ x ≤ 1.00, for example, x is 0.4, 0.5, 0.6, 0.8, 0.89, 0.9 or 1; preferably, 0 ≤ m ≤ 0.30, for example, m is 0, 0.05 or 0.1; preferably, 0 ≤ y ≤ 0.30, for example, y is 0.002, 0.004, 0.005, 0.01, 0.02, 0.05, 0.1 or 0.2; more preferably, 0.50 ≤ x + m ≤ 1.10, and even more preferably, 0.70 ≤ x + m ≤ 1.05, for example, 0.8, 0.9 or 1.
[0039] Wherein, the Li x+α A m TM 1-α-y M y O 2±δ Preferably, 0.2 ≤ x ≤ 1.00, for example, x is 0.4, 0.5, 0.6, 0.8, 0.89, 0.9 or 1; preferably, 0 < α < 0.50, for example, α is 0.05, 0.1, 0.2, 0.25 or 0.3; preferably, 0 ≤ m ≤ 0.3, for example, m is 0, 0.05 or 0.1; preferably, 0 ≤ y ≤ 0.30, for example, y is 0.002, 0.005, 0.006, 0.008, 0.01, 0.02, 0.05, 0.1 or 0.2.
[0040] Wherein, δ in the chemical formula represents the non-stoichiometric deviation of oxygen, used to characterize the degree of deviation of the actual oxygen content of the material from the ideal stoichiometric ratio 2; preferably, 0≤δ≤0.50, more preferably, 0≤δ≤0.20. When the actual oxygen content is less than 2, the subscript of oxygen in the chemical formula is 2-δ; when the actual oxygen content is greater than 2, the subscript of oxygen in the chemical formula is 2+δ.
[0041] In the chemical formula of the lithium-based crystalline oxide host material, A preferably includes one or more of Na, K, Rb, and Cs.
[0042] In the chemical formula of the lithium-based crystalline oxide host material, when TM includes a transition metal, the transition metal may include one or more of Co, Ni, Mn and Fe; when TM includes a main group metal, the main group metal may include Al and / or Mg.
[0043] The M in the chemical formula preferably includes one or more of alkaline earth metals, transition metals, rare earth elements, and p-block elements. M can form strong MO bonds and locally lattice-locked structures in the bulk phase; when M is an alkaline earth metal and / or a rare earth element, it can also be used to regulate the interlayer environment, oxygen stability, or surface reactivity.
[0044] The alkaline earth metal preferably includes one or more of Mg, Ca, Sr, and Ba; the transition metal preferably includes one or more of Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, W, Mn, Fe, Co, Ni, and Cu; the rare earth element preferably includes one or more of Sc, Y, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu; and the p-block element preferably includes one or more of B, Al, Ga, In, Si, Ge, Sn, P, Sb, and Bi.
[0045] In some specific embodiments, M in the chemical formula is preferably one or more of Ti, Zr, Nb, Ta, W, Mo, and Sn.
[0046] In some specific embodiments, the chemical formula of the lithium-based layered oxide host material is Li. 0.8 Co 0.99 Ti 0.01 O2, LiCo 0.99 Ti 0.01 O2, Li 0.9 [Ni 0.8 Co 0.1 Mn 0.1 ] 0.99 Ti 0.005 Mo 0.005 O2, Li 0.9 [Ni 0.8 Co 0.1 Mn 0.1 ] 0.99 Ti 0.005 Nb 0.005 O2, Li 0.9 [Ni 0.8 Co 0.1 Mn 0.1 ] 0.996 Ti 0.002 Mo 0.002 O2, Li 0.9 [Ni 0.8 Co 0.1 Mn 0.1 ] 0.98 Ti 0.01 Mo 0.01 O2 or Li 0.8+0.2 Ni 0.132Co 0.132 Mn 0.53 Ti 0.006 O2.
[0047] In this invention, the lithium-based layered oxide host material may be lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium nickel manganese oxide, lithium-rich manganese-based layered oxide, lithium-rich nickel-rich layered oxide, or Fe-containing layered oxide.
[0048] Wherein, for the lithium cobalt oxide, Co preferably accounts for more than 80% of the total molar amount of the transition metals; for the high-nickel ternary material, Ni preferably accounts for 60%-98% of the total molar amount of Ni, Co, and Mn; for the lithium-rich material, the molar ratio of Li to the total amount of the transition metals is preferably greater than 1.
[0049] In this invention, the crystalline phase of the lithium-based layered oxide host material may include one or more of O3, O2, T2, O6, and their distorted layered structures, preferably O3 / O2, O3 / T2, O2 / T2, O2 / O6, or a composite structure of three or more phases. Different phase regions may coexist within the same single particle or be distributed in different primary particles or different layers; the phase interface may be coherent, semi-coherent, or incoherent.
[0050] In this invention, the chemical formula of the composite oxide reconstructed interface layer may include A′B′O. 3±δ Li ρ A′ q B′O 3±δ A′2B′O 4±δ A′2B′2O 7±δ and A′2B′B″O 6±δ One or more of the following types of composite oxides.
[0051] In the chemical formula of the reconstructed interface layer of the composite oxide, the A′-site element preferably includes one or more of La, Ca, Sr, Ba, Ce, Pr, Nd, Gd, Y, Sm, and Bi; the B′-site element and / or the B″-site element are generally metal elements (TM, M) near the surface of the lithium-based crystalline oxide host material, preferably including one or more of Ti, Zr, Hf, Nb, Ta, W, Mo, Sn, Co, Ni, Mn, Fe, Cr, V, Ga, In, and Al; the B′-site element and the B″-site element are preferably different elements.
[0052] When the element at the A′ site is Ca and the element at the B′ site is Ti, the composite oxide reconstructed interface layer can be a Ca-Ti-O interface; when the element at the A′ site is La and the element at the B′ site is Co, the composite oxide reconstructed interface layer can be a La-Co-O interface; when the element at the A′ site is La and the elements at the B′ site are Ni, Co, and Mn, the composite oxide reconstructed interface layer can be a La-Ni / Co / Mn-O composite interface.
[0053] The interface phase of the composite oxide reconstructed interface layer may include one or more of CaTiO3, CaZrO3, CaSnO3, LaCoO3, LaNiO3, LaMnO3, LaFeO3, LaTiO3, LaAlO3, La2NiMnO6, and Li-La-Ti-O.
[0054] In this invention, the thickness of the composite oxide reconstructed interface layer can be 0.3-500 nm, preferably 1-100 nm, for example 5 nm, 6 nm, 8 nm, 10 nm, 20 nm or 50 nm.
[0055] In this invention, the composite oxide reconstructed interface layer can be formed by in-situ reaction of an external A′ source with the B′ site element and / or B″ site element near the surface of the lithium-based morphological oxide host material, or by simultaneously adding an external A′ source and a B′ source to control the interface phase composition.
[0056] In this invention, the molar amount of the A′ site element in the composite oxide reconstructed interface layer is preferably 0.01%-15% compared with the total molar amount of the main skeleton metal in the lithium-based crystalline oxide host material, more preferably 0.05%-5%, for example 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.8%, 1%, 2% or 3%.
[0057] In this invention, the molar amount of the B′ site element in the composite oxide reconstructed interface layer is preferably 0.01%-15% compared with the total molar amount of the main skeleton metal in the lithium-based crystalline oxide host material, more preferably 0.05%-5%, for example 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.8%, 1%, 2% or 3%.
[0058] In this invention, the functional coating layer can be at least one of a continuous layer, a quasi-continuous layer, a mesh layer, and an island-like connected layer. A continuous layer refers to a coating material forming a continuously extending film-like structure along the surface of the object being coated within the adopted characterization scale and representative observation area. The regions are interconnected, and there are essentially no identifiable through-pores, cracks, or interruptions that could directly expose the underlying material. A quasi-continuous layer refers to a coating material that is generally film-like and forms a main continuous phase within the representative observation area, but with isolated pinholes, cracks, thinning areas, or interruptions in certain local areas. These uncovered areas are not interconnected and do not disrupt the overall in-plane continuity of the coating layer. A quasi-continuous layer does not include structures forming a through-mesh framework. A mesh layer refers to a coating material that extends along the surface of the object being coated primarily in strip-like, branch-like, vein-like, or intersecting connecting units, forming a continuous mesh framework that penetrates the representative observation area. The mesh framework has multiple identifiable pores, windows, or uncovered areas, thus not constituting a complete or quasi-complete film-like continuous phase. The island-like connected layer refers to a coating material mainly distributed on the surface of the coated object as independent island-like, dot-like, block-like, or patch-like units, wherein at least some adjacent units form one or more connected clusters through neck connections, bridging structures, or local contact, but the connected clusters do not form a continuous membrane structure or continuous network skeleton that runs through the representative observation area. The determination of the aforementioned continuous layer, quasi-continuous layer, network layer, and island-like connected layer is based on the dominant morphology of the coating material and its in-plane connectivity within the representative observation area: continuous and quasi-continuous layers are mainly composed of membrane structures, the difference between them being the presence or absence of identifiable local interruptions; network layers are mainly composed of linear or strip-like skeletons that run through the observation area; island-like connected layers are mainly composed of locally connected island-like units and do not form a continuous structure that runs through the observation area.
[0059] In this invention, the functional coating layer is located outside and in direct contact with the composite oxide reconstructed interface layer. The functional coating layer can be a single material layer, a composite material layer, or a stack formed by two or more sub-layers: when the functional coating layer uses two or more materials, the materials can be mixed and dispersed, form an interpenetrating network, be distributed in a gradient along the thickness direction, or sequentially form multiple sub-layers.
[0060] In this invention, the functional coating layer is located outside the composite oxide reconstructed interface layer and can cover the outer surface of particles or particle aggregates formed by one or more primary particles; wherein, the composite oxide reconstructed interface layer can be formed on the surface of at least a portion of the primary particles.
[0061] In this invention, the primary particle refers to a single grain with a continuous crystal framework or a grain unit composed of a small number of orientation-related crystal domains; the particle or the particle agglomerate can be a single crystal particle or a secondary particle composed of multiple primary particles. The composite oxide reconstructed interface layer is preferably formed on at least a portion of the primary particle surface; the functional coating layer preferably covers the outermost surface of the secondary particle or the primary particle agglomerate.
[0062] In this invention, the functional coating layer and the composite oxide reconstructed interface layer can be combined through at least one of the following methods: physical bonding, chemical bonding, local element interdiffusion, and amorphous phase wetting.
[0063] In this invention, the coating material in the functional coating layer preferably exists in at least one of the following forms: particulate phase, continuous phase, short-range ordered phase, amorphous phase, and interpenetrating network.
[0064] In this invention, the thickness of the functional coating layer can be 0.5-100 nm, preferably 0.5-20 nm, for example 0.5 nm, 1 nm, 2 nm, 5 nm, 10 nm or 20 nm.
[0065] In this invention, the mass percentage of the functional coating layer can be 0.05%-10%, preferably 0.1%-5%, for example 0.1%, 0.2%, 0.26%, 0.35%, 0.42%, 0.5%, 0.6%, 0.8%, 0.83%, 1%, 1.2%, 1.5% or 2%; the mass percentage refers to the percentage of the mass of the functional coating layer to the sum of the masses of the lithium-based morphological oxide host material and the composite oxide reconstructed interface layer.
[0066] In this invention, the solid electrolyte material in the functional coating layer is preferably an oxide solid electrolyte and / or a polymer-inorganic composite solid electrolyte, wherein the inorganic phase in the polymer-inorganic composite solid electrolyte is a non-halide solid electrolyte. The non-halide solid electrolyte refers to an inorganic solid electrolyte with a main structure of metal fluorides, chlorides, bromides, or iodides, and is not used to exclude organic polymer materials containing halogen elements in their molecular structure.
[0067] Preferably, the inorganic phase in the polymer-inorganic composite solid electrolyte is at least one of oxide solid electrolyte, phosphate solid electrolyte, borate solid electrolyte, and silicate solid electrolyte.
[0068] The oxide solid electrolyte may include garnet-type Li7La3Zr2O 12 Garnet-type Li7La3Zr2O 12 Dopant, NASICON type Li1+x1 Al x1 Ti 2-x1 (PO4)3 (0≤x1≤0.5), Li 1+x2 Al x2 Ge 2-x2 (PO4)3 (0≤x2≤0.5), perovskite-type Li 3x3 La 2 / 3-x3 At least one of TiO3 (0 < x3 ≤ 1 / 6) and LiPON. The presence of the solid electrolyte material provides a lithium-ion transport pathway.
[0069] Furthermore, in the Li 1+x1 Al x1 Ti 2-x1 In (PO4)3, preferably, 0.1 ≤ x1 ≤ 0.5, more preferably, 0.2 ≤ x1 ≤ 0.4; in the Li 1+x2 Al x2 Ge 2-x2 In (PO4)3, preferably, 0.1 ≤ x2 ≤ 0.5, more preferably, 0.3 ≤ x2 ≤ 0.5; in the Li 3x3 La 2 / 3-x3 In TiO3, preferably, 0.05≤x3≤0.16, and more preferably, 0.08≤x3≤0.13.
[0070] Furthermore, the garnet-type Li7La3Zr2O 12 Dopant such as Li 6.4 La3Zr 1.4 Ta 0.6 O 12 (LLZTO).
[0071] In this invention, the compound containing polyanionic structural units in the functional coating layer preferably includes at least one of the following: discrete oxygen-containing anions, condensed oxygen-containing anions, and oxygen-containing network structural units formed by at least one of the central atoms of P, B, Si, and S with O. The presence of the compound containing polyanionic structural units can stabilize the surface oxygen framework, provide cation coordination sites, and reduce interfacial side reactions.
[0072] The oxygen-containing network structural unit may have a negative charge compensated by cations, or it may be connected to adjacent structural units through bridging oxygen to form a chain-like, ring-like, layered, or three-dimensional network structure.
[0073] Preferably, the oxygen-containing network structural unit includes at least one of phosphorus-oxygen tetrahedral unit PO4, tricoordinated boron-oxygen unit BO3, tetracoordinated boron-oxygen unit BO4, and silicon-oxygen tetrahedral unit SiO4. When the oxygen-containing network structural unit forms a condensation structure or an amorphous network structure through bridging oxygen, its local formal charge can vary with the number of bridging oxygen, the number of non-bridging oxygen, and the connection mode of adjacent structural units, and is not limited to the formal charge of the corresponding isolated oxygen-containing anion. In the oxygen-containing network structural unit, adjacent structural units can be connected by one or more bridging methods selected from P—O—P, B—O—B, Si—O—Si, P—O—B, P—O—Si, B—O—Si, and S—O—B.
[0074] In this invention, the polyanionic structural units in the functional coating layer preferably include orthophosphate (PO4) in the compound containing polyanionic structural units. 3- pyrophosphate P2O7 4- BO3- orthoborate 3- SiO4 orthosilicate 4- and sulfate SO4 2- At least one of the following; the cations in the compound containing polyanionic structural units preferably include one or more of lithium ions, sodium ions, potassium ions, ammonium ions, magnesium ions, calcium ions, strontium ions, barium ions, aluminum ions and rare earth metal ions, more preferably one or more of lithium ions, ammonium ions, magnesium ions, calcium ions and aluminum ions.
[0075] In this invention, the compound containing polyanionic structural units in the functional coating layer can be crystalline, low-crystallinity, or amorphous.
[0076] In this invention, the inorganic glassy material is preferably a lithium-containing glassy network material, and more preferably includes at least one of lithium phosphooxy glassy material, lithium boronooxy glassy material, lithium boron phosphooxy glassy material, lithium silicon oxy glassy material, lithium silicon phosphooxy glassy material, and lithium aluminum phosphooxy glassy material. The composition of the lithium-containing glassy network material can be represented as Li-PO, Li-BO, Li-BPO, Li-Si-O, Li-Si-PO, and Li-Al-PO, respectively. The aforementioned composition indicates the main elements contained in the material and does not limit the elements to have a unique and fixed stoichiometric ratio. In this invention, the amorphous oxide is preferably an amorphous inorganic oxide, and more preferably includes at least one of amorphous B2O3, amorphous SiO2, amorphous Al2O3, and amorphous ZrO2.
[0077] In this invention, the inorganic glassy material and the amorphous oxide can improve the integrity of the coating and buffer the interfacial stress.
[0078] In this invention, the metal oxide in the functional coating layer refers to a solid oxide material that mainly maintains the metal-oxygen crystal framework after heat treatment, preferably including at least one of γ-Al2O3, α-Al2O3, δ-Al2O3, θ-Al2O3, TiO2, ZrO2, Nb2O5, Ta2O5, MgO, ZnO, CeO2, SnO2, WO3, MoO3 and their doped or defect derivatives.
[0079] In this invention, the carbonaceous material in the functional coating layer refers to the material that, after heat treatment, is mainly composed of sp... 2 Carbon and / or sp 3 Materials consisting of a solid carbon skeleton. The carbonaceous material preferably includes at least one of amorphous carbon, disordered layered carbon, hard carbon, soft carbon, graphitized carbon, heteroatom-doped carbon, and polymer-derived carbon; the heteroatoms preferably include at least one of N, B, P, and S.
[0080] In this invention, the heat-treated convertible organic polymer material in the functional coating layer refers to a solid material formed after heat treatment of organic polymer materials, which still retains the organic polymer backbone, ladder segments or cross-linked organic framework and has not been completely carbonized.
[0081] In this invention, the polymer source corresponding to the heat-treated convertible organic polymer material in the functional coating layer before heat treatment may include one or more of the following: nitrile polymers, imide-containing polymers, fluoropolymers, acrylate polymers, polymers containing hydroxyl or ether bonds, nitrogen-containing heterocyclic polymers, aromatic thermosetting polymers, natural polymers and their derivatives.
[0082] This invention provides a method for preparing a multiphase fast-transport layered cathode material, comprising the following steps:
[0083] Method 1:
[0084] (1) The metal TM source, the non-lithium alkali metal A source and the doped element M source are dry-mixed and then heat-treated to obtain a layered oxide precursor;
[0085] (2) The layered oxide precursor, lithium source and interface reconstruction element A′ source are dry-mixed and then heat-treated to obtain lithium-based layered oxide intermediate material;
[0086] (3) The lithium-based layered oxide intermediate material is coated with a coating material source to obtain the multiphase fast transport layered cathode material;
[0087] Method 2:
[0088] (1) The metal TM source, the non-lithium alkali metal A source and the doped element M source are dry-mixed and then heat-treated to obtain a layered oxide precursor;
[0089] (2) The mixture of the layered oxide precursor and the lithium source is subjected to topological exchange to obtain a lithium-based layered oxide material;
[0090] (3) The lithium-based morphological oxide material, lithium source and interface reconstruction element A′ source are dry-mixed and then heat-treated to obtain lithium-based morphological oxide intermediate material;
[0091] (4) The lithium-based layered oxide intermediate material is coated with a coating material source to obtain the multiphase fast transport layered cathode material;
[0092] When the main material of the multiphase fast transport layered cathode material is a metastable phase material, method one is used; when the main material of the multiphase fast transport layered cathode material is a stable phase material, either method one or method two is used.
[0093] The TM element in the metal TM source includes transition metals and / or main group metals that constitute the main framework of the layered oxide precursor; the M element in the doping element M source includes one or more of alkaline earth metals, transition metals, rare earth elements, and p-block elements; the A′ element in the interface reconstruction element A′ source includes metal elements capable of forming a composite oxide interface structure with metal elements near the surface of the host material; the coating material source includes at least one of solid electrolyte source, polyanionic compound source, inorganic glassy material source, amorphous oxide source, metal oxide source, carbon source, and polymer source.
[0094] In the preparation method of this invention, a non-lithium alkali metal layered oxide precursor with adjustable alkali metal content, interlayer spacing, oxygen layer stacking mode, transition metal framework, particle morphology, and doping environment is first constructed through a dry solid-state reaction using a transition metal source (e.g., oxide) as the main raw material; subsequently, Li... + The topological exchange with non-lithium alkali metal ions in the precursor at least partially preserves the transition metal-oxygen framework and particle morphology; and by utilizing the non-lithium alkali metals remaining near the surface after ion exchange, the framework metal elements and doping elements in the host, and the external interface control elements, a composite oxide reconstructed interface layer is formed in situ bonded to the host during the topological exchange process or subsequent heat treatment; finally, the multiphase fast transport layered cathode material is obtained by coating it with a coating material source.
[0095] In this invention, the main material of the multiphase fast transport layered cathode material refers to the lithium-based layered oxide portion of the multiphase fast transport layered cathode material, rather than the surface coating layer portion.
[0096] In this invention, the metastable phase material refers to a material whose crystal phase has a higher Gibbs free energy than the O3 stable phase, and can exist stably in kinetics, but will spontaneously transform into a single O3 stable phase at high temperatures. The crystal phase of the metastable phase material typically includes one or more of O2, T2, O6, and their distorted layered structural domains.
[0097] In this invention, the stable phase material generally refers to a material whose crystal phase is the O3 stable phase.
[0098] In this invention, the transition metal in the metal TM source may include one or more of Co, Ni, Mn and Fe; the main group metal may include Al and / or Mg.
[0099] In this invention, the metal TM source may be an oxide of metal TM and / or a salt that can decompose to form the corresponding metal TM oxide during heat treatment.
[0100] The oxide of the metal TM preferably includes one or more of Co3O4, CoO, Co2O3, NiO, Ni2O3, MnO2, Mn2O3, Mn3O4, Fe2O3, Fe3O4, Al2O3, and MgO.
[0101] The salts that can decompose to form corresponding metal TM oxides during heat treatment are not multi-component hydroxides or multi-component carbonate particles formed by liquid-phase co-precipitation.
[0102] The type of oxide of the metal TM can be determined according to the type of the layered oxide precursor; for example, when the layered oxide precursor is a lithium cobalt oxide precursor, the oxide source of the metal TM is, for example, Co3O4; when the layered oxide precursor is a lithium nickel cobalt manganese oxide precursor, the oxide source of the metal TM is, for example, NiO, Co3O4 and MnO2.
[0103] In this invention, the element A in the non-lithium alkali metal A source preferably includes one or more of Na, K, Rb, and Cs. The non-lithium alkali metal A source can be a salt of A and / or a base of A; the salt of A preferably includes one or more of Na₂CO₃, NaNO₃, NaHCO₃, K₂CO₃, KNO₃, KHCO₃, Rb₂CO₃, RbNO₃, Cs₂CO₃, and CsNO₃; the base of A preferably includes one or more of NaOH, KOH, RbOH, and CsOH.
[0104] In this invention, the molar ratio of element A in the non-lithium alkali metal A source to the total molar amount of element TM in the metal TM oxide source and element M in the doped element M source can be (0.1-2.0):1, for example, 0.5:1, 0.6:1, 0.8:1, 0.89:1, 0.9:1, 1:1, 1.04:1, 1.1:1, or 1.2:1. The amount of the non-lithium alkali metal A source used is generally 0.5%-5% excess over the target theoretical amount, for example, 2%, 3%, or 4%.
[0105] In this invention, the M element in the dopant element M source preferably includes one or more of the alkaline earth metals Mg, Ca, Sr, and Ba; the transition metals preferably include one or more of Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, and W; the rare earth elements preferably include one or more of Sc, Y, La, Ce, Pr, Nd, Sm, and Gd; and the P-block elements preferably include one or more of B, Al, Ga, In, Si, Ge, Sn, P, Sb, and Bi.
[0106] In some specific embodiments, the M element in the dopant element M source preferably includes one or more of Ti, Zr, Nb, Ta, W, Mo, Sb, and Sn.
[0107] In this invention, the dopant element M source can be an oxide of M, such as one or more of TiO2, MoO3, Nb2O5, ZrO2, Ta2O5, Sb2O3, Sb2O5, WO3 and SnO2.
[0108] In this invention, the molar ratio of element M in the doped element M source to the total molar amount of element TM in the metal TM oxide source and element M in the doped element M source can be 0.05%-5%, for example 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.75%, 0.8%, 1%, 1.5%, 2% or 3%.
[0109] In some specific implementations, the dopant element M source is TiO2, TiO2 and MoO3 or TiO2 and Nb2O5.
[0110] In some preferred embodiments, when the dopant element M source is TiO2 and MoO3, the molar ratio of TiO2 to MoO3 can be 1:(0.5-1.5), for example 1:0.8, 1:1 or 1:1.2.
[0111] In some preferred embodiments, when the dopant element M source is TiO2 and Nb2O5, the molar ratio of TiO2 to Nb2O5 can be 1:(0.5-1.5), for example 1:0.8, 1:1 or 1:1.2.
[0112] In this invention, the TM element in the metal TM source is the main metal component constituting the main framework of the layered oxide precursor. It forms a continuous metal-oxygen framework with oxygen and is used to determine the basic stoichiometry, main crystal phase, and main structural type of the layered oxide precursor. The M element in the dopant element M source is an additional regulatory component introduced relative to the predetermined main framework composition. Its content is lower than that of the TM element constituting the main framework, and it exists in one or more ways, such as replacing some metal sites in the main framework, occupying interlayer sites or defect-related sites, accumulating at grain boundaries, and forming local coordination structures in the main framework. The M element is used to enhance local M-O bonding, stabilize the oxygen framework, regulate the local coordination environment and lattice strain, and suppress one or more of cation migration, oxygen loss, or unfavorable phase transitions. The candidate element ranges of the TM element and the M element may partially overlap; however, for any specific material composition, the TM element and the M element are distinguished according to their stoichiometric status in the target chemical formula, their purpose of addition, and their relative content. When the same chemical element is present in a predetermined host framework composition and is also introduced additionally relative to that predetermined host framework composition, the portion constituting the basic stoichiometry of the predetermined host framework is classified as TM element, and the portion introduced additionally beyond the basic stoichiometry for doping control purposes is classified as M element. The content of TM element or M element is not counted repeatedly; that is, an element with a certain content cannot be included in both the content range of TM element and the content range of M element. The molar amount of M element compared to the total molar amount of TM element and M element is preferably 0.05%–30%, more preferably 0.05%–5%.
[0113] In step (1) of Method 1 and / or step (1) of Method 2, a lithium source may be added before the dry mixing. The lithium source may be one or more of LiNO3, LiCl, LiBr, LiI, LiOH, Li2CO3, Li2O, LiCH3COO, and Li2SO4; the molar ratio of element A in the non-lithium alkali metal A source to element Li in the lithium source may be 1:(0-1), for example 1:0.1, 1:0.2, 1:0.25, 1:0.3, 1:0.4, or 1:0.5; when the lithium source is added in this step, the chemical formula of the resulting lithium-based crystalline oxide substrate is generally represented as Li x+α A m TM 1-α-y M y O 2±δWhen no lithium source is added in this step, the chemical formula of the resulting lithium-based crystalline oxide substrate is generally represented as Li. x A m TM 1-y M y O 2±δ .
[0114] In step (1) of method one and / or step (1) of method two, the types and amounts of the metal TM oxide source, the non-lithium alkali metal A source and the dopant element M source are generally added according to the target chemical formula of the layered oxide precursor in stoichiometric ratio.
[0115] In some specific embodiments, the layered oxide precursor is P2 phase Na. 0.8 Co 0.99 Ti 0.01 O2, P2 phase Na 1.04 Co 0.99 Ti 0.01 O2, Na 0.9 [Ni 0.8 Co 0.1 Mn 0.1 ] 0.99 Ti 0.005 Mo 0.005 O2, Na 0.86 K 0.04 [Ni 0.8 Co 0.1 Mn 0.1 ] 0.99 Ti 0.005 Mo 0.005 O2 or K 0.8 Li 0.2 Ni 0.132 Co 0.132 Mn 0.53 Ti 0.006 O2.
[0116] In steps (1) and (2) of Method 1, and steps (1) and (3) of Method 2, the dry mixing generally refers to directly mixing the solid powders of each raw material without relying on a large volume of solution coating. During the dry mixing process, a small amount of liquid medium may be added; to maintain the dry mixing characteristics, the amount of liquid medium is preferably no more than 10% of the total solid mass, more preferably no more than 3%, and most preferably no liquid medium is added. The dry mixing method may be grinding (e.g., mortar and pestle grinding), planetary ball milling, vibratory ball milling, mechanical fusion, airflow mixing, high-speed shear mixing, jet mixing, or roller pressing mixing.
[0117] In certain specific implementations, in step (1) of method one, step (1) of method two, or step (3) of method two, the dry mixing method is planetary ball milling. The rotation speed of the dry ball milling can be 200-800 rpm, for example 300 rpm, 400 rpm, or 500 rpm; the dry ball milling time can be 1-6 h, for example 2 h, 3 h, or 4 h; the diameter of the grinding balls used in the dry ball milling process can be 2-10 mm, for example 5 mm; the ball-to-material ratio can be (5-15):1, for example 10:1; the ball-to-material ratio refers to the ratio of the mass of the grinding balls to the mass of the sample powder to be processed.
[0118] In step (2) of Method 1 and / or step (2) of Method 2, the dry mixing method is preferably grinding. The grinding time can be 1-30 min, preferably 1-10 min, for example 2 min, 5 min or 8 min.
[0119] In steps (1) and (2) of Method 1, and steps (1) and (3) of Method 2, the heat treatment is generally carried out in a sintering furnace; the atmosphere of the heat treatment can be selected from air, oxygen, oxygen-containing mixed gas, nitrogen, argon, carbon dioxide or carbon dioxide-containing mixed gas according to the target valence state of the metal elements in the target material, the degree of oxygen non-stoichiometry, the thermal decomposition characteristics of the precursor and the formation requirements of the composite oxide reconstruction interface layer.
[0120] Wherein, when the transition metal elements in the target material need to maintain a high average valence state, reduce oxygen vacancies, increase lattice oxygen content and / or suppress the mixing of transition metal and lithium cations, the heat treatment atmosphere is preferably oxygen or an oxygen-containing mixture with an oxygen content higher than that of air.
[0121] When the target material can be formed and exist stably under the partial pressure of oxygen in air, and there is no need to further increase the average valence state of the transition metal or reduce the oxygen vacancy concentration, air is preferably selected as the heat treatment atmosphere.
[0122] When it is necessary to adjust the oxygen partial pressure between air and pure oxygen to take into account the oxidation of metal elements, lattice oxygen content, phase structure stability and interfacial reaction degree in the target material, the heat treatment atmosphere is preferably an oxygen-containing mixed gas; the oxygen-containing mixed gas can be a mixture of oxygen, nitrogen and / or argon.
[0123] When the metal elements in the target material need to maintain a relatively low valence state, inhibit further oxidation, regulate oxygen vacancy content, and / or avoid excessive oxidation of precursors or interface control elements, nitrogen or argon is preferably selected as the heat treatment atmosphere. Nitrogen can be selected when it does not react significantly with the raw materials or intermediate products; argon is preferred when higher chemical inertness is required or when nitrogen participation in the reaction needs to be avoided.
[0124] When it is necessary to adjust the oxygen content, oxygen vacancies, and carbonate content of the host material or the interface layer through gas-solid reaction, or to form a carbonate-containing surface and / or interface reconstruction region, the heat treatment atmosphere may be carbon dioxide or a mixture containing carbon dioxide.
[0125] In step (2) of Method 2, the topology exchange is generally carried out in a sintering furnace; the atmosphere of the heat treatment can be oxygen or an oxygen-containing mixture with an oxygen content higher than that of air.
[0126] In certain specific implementations, in steps (1) and (2) of method one, and steps (1), (2), and (3) of method two, the atmosphere of the heat treatment or the topological exchange can be oxygen or an oxygen-containing mixture with an oxygen content higher than that of air.
[0127] In step (1) of Method 1 and / or step (1) of Method 2, the temperature of the heat treatment can be 450-1100℃, preferably 500-1200℃, for example 550℃, 600℃, 650℃, 700℃, 750℃, 800℃, 810℃, 820℃, 835℃, 850℃, 900℃ or 950℃; the time of the heat treatment can be 0.2-48h, preferably 1-24h, for example 2h, 3h, 4h, 5h, 8h, 10h, 12h, 16h or 18h.
[0128] In step (1) of Method 1 and / or step (1) of Method 2, the heat treatment may be a one-step calcination or a multi-step calcination.
[0129] The calcination temperature in the first step can be 500-1200℃, for example 550℃, 600℃, 650℃, 700℃, 750℃, 800℃, 810℃, 820℃, 835℃, 850℃, 900℃ or 950℃; the calcination time in the first step can be 0.2-48h, preferably 1-24h, for example 2h, 3h, 4h, 5h, 8h or 10h, 12h, 16h or 18h.
[0130] The two-step calcination preferably includes the following process: first, holding at 500-700℃ for 1-6 hours, and then continuing to raise the temperature to 750-1200℃ and holding for 1-24 hours.
[0131] In some specific implementations, the two-step calcination can be performed by first holding the temperature at 600°C for 4 hours, and then continuing to raise the temperature to 900°C and hold it for 5 hours.
[0132] In step (1) of Method 1 and / or Method 2, the pre-configuration degree of the layered oxide precursor can be adjusted by changing the type and content of the non-lithium alkali metal A. When the non-lithium alkali metal A is Na, it is suitable for forming P2, P3 or O3 layered precursors; K, Rb and Cs have larger ionic radii, which can expand the interlayer spacing and increase the degree of freedom of layer slip; mixed alkali metals can generate site differences and local disorder at different sites, providing structural seeds for subsequent multiphase formation.
[0133] In step (2) of method one and / or step (2) of method two, the lithium source may be one or more of LiNO3, LiCl, LiBr, LiI, LiOH, Li2CO3, Li2O, LiCH3COO and Li2SO4; the molar ratio of Li element in the lithium source to A element in the non-lithium alkali metal A source in the layered oxide precursor may be (1-30):1, preferably (1-15):1, for example 1.5:1, 2:1, 2.5:1, 3:1, 5:1, 8:1 or 10:1.
[0134] In some specific implementations, in step (2) of method one and / or step (2) of method two, when the lithium source is a mixed lithium salt of LiNO3 and LiCl, the molar ratio of LiNO3 to LiCl can be (5-10):1, for example 6:1, 7.3:1 or 8:1.
[0135] In step (2) of method one and / or step (3) of method two, the A′ element in the interface reconstruction element A′ source preferably includes one or more of La, Ca, Sr, Ba, Ce, Pr, Nd, Gd and Y; the interface reconstruction element A′ source preferably includes one or more of oxides, hydroxides, carbonates, nitrates, hydrochlorides, acetates and precursors that can thermally decompose to form the corresponding oxides of the corresponding A′ element.
[0136] When the A′ element in the interface reconstruction element A′ source is Ca, the A′ source can be one or more of CaO, CaCO3, Ca(OH)2, Ca(NO3)2, Ca(CH3COO)2 and CaCl2.
[0137] When the A′ element in the interface reconstruction element A′ source is Ba, the A′ source can be one or more of BaCO3, Ba(NO3)2 and BaCl2.
[0138] When the A′ element in the interface reconstruction element A′ source is Sr, the A′ source can be SrCO3 and / or Sr(NO3)2.
[0139] When the A′ element in the interface reconstruction element A′ source is La, the A′ source can be one or more of La2O3, La(OH)3, La(NO3)3 and La(CH3COO)3.
[0140] When the A′ element in the interface reconstruction element A′ source is Ce, the A′ source can be CeO2; when the A′ element in the interface reconstruction element A′ source is Pr, the A′ source can be Pr6O. 11 When the A′ element in the interface reconstruction element A′ source is Nd, the A′ source can be Nd2O3; when the A′ element in the interface reconstruction element A′ source is Y, the A′ source can be Y2O3.
[0141] In step (2) of Method 1 and / or step (3) of Method 2, a B′ source and / or a B″ source may be added before the dry mixing; the B′ element in the B′ source and / or the B″ element in the B″ source may include one or more of Ti, Zr, Hf, Nb, Ta, W, Mo, Sn, Co, Ni, Mn, Fe, Cr, V, Ga, In, and Al. Preferably, the B′ element and the B″ element are different elements.
[0142] The B′ source and / or B″ source may be one or more of the oxides, hydroxides, carbonates, nitrates, acetates, and precursors that can be thermally decomposed to form the corresponding oxides of the corresponding B′ and / or B″ elements.
[0143] In some specific embodiments, the B′ source and / or B″ source is one or more of TiO2, ZrO2, HfO2, Nb2O5, Ta2O5, WO3, MoO3, SnO2, Co3O4, NiO, MnO2, Fe2O3, Cr2O3, V2O5, Al2O3, Ga2O3, and In2O3.
[0144] In step (2) of Method 1, the total molar amount of A′ element in the A′ source and non-alkali metal elements (TM element + M element) in the layered oxide precursor is preferably 0.01%-15%, more preferably 0.05%-5%, for example 0.1%, 0.2%, 0.3%, 0.5%, 0.8%, 1% or 2%.
[0145] In step (3) of Method 2, the molar ratio of the A′ element in the A′ source to the total molar amount of the non-alkali metal elements (TM element + M element) in the lithium-based layered oxide material is preferably 0.01%-15%, more preferably 0.05%-5%, for example 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.8%, 1%, 2% or 3%.
[0146] In Method 1, in step (2), the temperature of the heat treatment can be 200-400℃, for example 250℃, 260℃, 270℃, 280℃, 285℃, 290℃, 300℃, 320℃ or 350℃; the time of the heat treatment can be 10min-8h, for example 20min, 30min, 1h, 2h, 3h, 4h, 5h or 6h.
[0147] In Method 2, in step (2), the preparation method of the mixture of the layered oxide precursor and the lithium source can be conventional in the field. Generally, the two are directly ground and mixed evenly.
[0148] In Method 2, in step (2), the topological exchange can be molten salt exchange, solid-phase exchange, or solid-liquid synergistic exchange. The temperature of the topological exchange can be 80-900℃; the time of the topological exchange can be 1 min-24 h.
[0149] The molten salt exchange refers to ion exchange performed in a molten salt state using a mixture of a lithium source of metal salts and the layered oxide precursor.
[0150] The temperature of the ion exchange generally needs to be higher than the melting point of the lithium source of the metal salt, preferably more than 10°C higher, and more preferably 20-200°C higher than the melting point of the lithium source of the metal salt, for example, 30°C, 40°C, 45°C, 60°C, 80°C, 100°C, 121°C or 150°C higher than the melting point; the time of the ion exchange can be 1-12 hours, for example 2 hours, 3 hours, 4 hours, 5 hours or 6 hours.
[0151] When the lithium source of the metal salt is lithium nitrate, the temperature of the ion exchange can be 274-450℃, for example 300℃, 350℃, 385℃ or 400℃.
[0152] When the lithium source of the metal salt is lithium chloride, the temperature of the ion exchange can be 620-750℃, for example 630℃, 640℃, 650℃, 680℃, 700℃ or 720℃.
[0153] During the ion exchange, preferably, the mixture of the lithium source of the metal salt and the layered oxide precursor is placed directly in a reactor that has been preheated to the temperature for the ion exchange and kept at that temperature.
[0154] The solid-phase exchange refers to the process where the layered oxide precursor is mixed with a solid lithium source, and then subjected to heat treatment under conditions where the lithium source remains solid and the reaction system does not form a continuous liquid phase, so that the Li... + It diffuses into the layered oxide precursor through the solid-solid contact interface and exchanges with the non-lithium alkali metal ions therein.
[0155] Specifically, the solid-liquid synergistic exchange refers to the process where the layered oxide precursor remains in a solid state, while at least a portion of the lithium source, auxiliary salt, and / or liquid medium forms a liquid phase during ion exchange. This liquid phase promotes Li-ion exchange through wetting, permeation, and liquid-phase mass transfer. + Reaching the surface of the layered oxide precursor and cooperating with ion diffusion within the solid framework to complete Li + Exchange with non-lithium alkali metal ions.
[0156] In step (2) of Method 1, the cooling method after heat treatment and / or in step (2) of Method 2, the cooling method after the topological exchange can be natural cooling, furnace cooling, air quenching, metal plate quenching, liquid heat exchange cooling, liquid nitrogen quenching, or segmented cooling. The cooling rate after the topological exchange plays an important role in the phase composition. Rapid cooling is beneficial for freezing T2, O2, O6, stacking faults, and local micro-strain; slow cooling or subsequent high-temperature lithium replenishment crystallization is beneficial for improving the proportion of O3 phase and long-range order.
[0157] After the heat treatment in step (2) of Method 1 and / or the topological exchange in step (2) of Method 2, washing and drying are generally required. The solvent used for washing can be one or more of deionized water, ethanol, and isopropanol; the washing generally needs to be performed until the filtrate is close to neutral.
[0158] In Method 2, in step (3), the lithium source can be one or more of LiNO3, LiCl, LiBr, LiI, LiOH, Li2CO3, Li2O, LiCH3COO and Li2SO4; the molar percentage of Li element in the lithium source to the lithium-based crystalline oxide material can be 1%-30%, for example 2%, 5%, 10%, 15%, 20% or 25%.
[0159] In Method 2, in step (3), the temperature of the heat treatment can be 400-900℃, for example 500℃, 600℃, 700℃, 750℃ or 800℃; the time of the heat treatment can be 1-12h, for example 3h, 5h, 8h, 10h or 12h. After the heat treatment, it can generally be cooled naturally.
[0160] In Method 2, in step (3), the heat treatment can be a one-step calcination or a multi-step calcination.
[0161] The stepwise calcination can be a two-step calcination. Preferably, the two-step calcination includes the following process: first, holding at 450-600℃ for 1-6 hours, and then continuing to raise the temperature to 650-900℃ and holding for 1-6 hours.
[0162] In some specific implementations, the heat treatment may involve first holding at 500°C for 5 hours, and then continuing to heat to 750°C and holding for 5 hours; or, directly holding at 750°C for 5 hours.
[0163] In this invention, the main framework generally refers to the continuous lattice framework in the layered cathode material, which is composed of metal element TM, dopant element M and oxygen, excluding interlayer Li and residual non-lithium alkali metal A.
[0164] In step (3) of method one and / or step (4) of method two, the solid electrolyte source is preferably an oxide solid electrolyte and / or a polymer-inorganic composite solid electrolyte, wherein the inorganic phase in the polymer-inorganic composite solid electrolyte is a non-halogenated solid electrolyte.
[0165] Preferably, the inorganic phase in the polymer-inorganic composite solid electrolyte is at least one of oxide solid electrolyte, phosphate solid electrolyte, borate solid electrolyte, and silicate solid electrolyte.
[0166] The oxide solid electrolyte may include garnet-type Li7La3Zr2O 12 Garnet-type Li7La3Zr2O 12 Dopant, NASICON type Li 1+x1 Al x1 Ti 2-x1 (PO4)3 (0≤x1≤0.5), Li 1+x2 Al x2 Ge 2-x2 (PO4)3 (0≤x2≤0.5), perovskite-type Li 3x3 La 2 / 3-x3 At least one of TiO3 (0 < x3 ≤ 1 / 6) and LiPON. The presence of the solid electrolyte material provides a lithium-ion transport pathway.
[0167] In some specific embodiments, the solid electrolyte source is Li 6.4 La3Zr 1.4 Ta 0.6 O 12 .
[0168] In step (3) of Method 1 and / or step (4) of Method 2, the polyanionic compound source refers to a substance that contains polyanionic structural units or can form polyanionic structural units during subsequent drying and / or heat treatment. The polyanionic compound source preferably includes one or more of phosphoric acid, polyphosphoric acid, phosphates, boric acid, borates, silicates, and sulfates. The cations in the phosphates, borates, silicates, and sulfates preferably include one or more of lithium ions, sodium ions, potassium ions, ammonium ions, magnesium ions, calcium ions, strontium ions, barium ions, aluminum ions, and rare earth metal ions, more preferably one or more of lithium ions, ammonium ions, magnesium ions, calcium ions, and aluminum ions.
[0169] In some specific embodiments, the polyanionic compound source is lithium orthophosphate.
[0170] In step (3) of method one and / or step (4) of method two, the inorganic glassy material source preferably includes a mixture of "at least one of phosphorus source, boron source, silicon source and aluminum source" and lithium source.
[0171] The phosphorus source may include one or more of phosphoric acid, polyphosphoric acid, phosphorus pentoxide, ammonium phosphate, diammonium hydrogen phosphate, diammonium dihydrogen phosphate, lithium phosphate, lithium dihydrogen phosphate, dilithium hydrogen phosphate, lithium pyrophosphate, lithium metaphosphate, and organophosphate esters; the organophosphate ester is, for example, trimethyl phosphate and / or triethyl phosphate; the boron source may include one or more of boric acid, boron oxide, lithium metaborate, lithium tetraborate, sodium metaborate, sodium tetraborate, and borate esters; the borate ester is, for example, trimethyl borate and / or triethyl borate; the silicon source may include silicon dioxide, amorphous silicon dioxide, silica sol, colloidal silicon dioxide, etc. The source may include one or more of tetramethyl silicate, tetraethyl orthosilicate, lithium silicate, sodium silicate, and potassium silicate; the aluminum source may include one or more of alumina, amorphous alumina, aluminum hydroxide, boehmite, boehmite, aluminum sol, aluminum nitrate, aluminum acetate, aluminum isopropoxide, and aluminum sec-butoxide; the lithium source may include one or more of LiNO3, LiOH, LiOH·H2O, Li2CO3, Li2O, LiCH3COO, Li2SO4, Li3PO4, LiH2PO4, LiBO2, Li2B4O7, Li2SiO3, and Li4SiO4. The amount of phosphorus source, boron source, silicon source, aluminum source, and lithium source is not particularly limited.
[0172] In some specific embodiments, the inorganic glassy material source is a mixture of LiNO3, H3BO3 and NH4H2PO4.
[0173] In some preferred embodiments, when the inorganic glassy material source is a mixture of LiNO3, H3BO3 and NH4H2PO4, the mass ratio of LiNO3, H3BO3 and NH4H2PO4 is (1.5-8):1:(1.5-4).
[0174] In some preferred embodiments, when the inorganic glassy material source is a mixture of LiNO3, H3BO3 and NH4H2PO4, the mass ratio of LiNO3, H3BO3 and NH4H2PO4 is 5.3:1:2.8, 2.7:1:2.8 or 10.7:1:2.8.
[0175] In this invention, the polyanionic compound source and the inorganic glassy material source can be distinguished based on their expected products and intended uses in specific embodiments, rather than solely on the raw material names. The polyanionic compound source primarily uses phosphate, borate, silicate, or sulfate compounds with relatively defined compositions as the main material form, while the inorganic glassy material source primarily uses a non-long-range ordered inorganic network formed by the connection of multiple oxygen-containing structural units. The distinction between the two is not solely based on the presence or absence of local structural units of PO4, BO3, BO4, or SiO4. The same substance can serve as a polyanionic compound source, or as a network element source and / or lithium source within the inorganic glassy material source. For example, when Li3PO4 directly forms or retains a phosphate polyanionic compound coating layer, it is classified as a polyanionic compound source; when Li3PO4 reacts with other network element sources to form an inorganic glassy network material, it can be classified as an inorganic glassy material source. For the same specific feed, the substance is classified into the corresponding coating material source according to its primary use, and its addition amount is not repeatedly calculated.
[0176] In step (3) of method one and / or step (4) of method two, the amorphous oxide source is preferably an amorphous inorganic oxide, and more preferably includes at least one of amorphous B2O3, amorphous SiO2, amorphous Al2O3 and amorphous ZrO2.
[0177] In step (3) of method one and / or step (4) of method two, the metal oxide source may include at least one of γ-Al2O3, α-Al2O3, δ-Al2O3, θ-Al2O3, TiO2, ZrO2, Nb2O5, Ta2O5, MgO, ZnO, CeO2, SnO2, WO3, MoO3 and their doped or defective derivatives.
[0178] In step (3) of Method 1 and / or step (4) of Method 2, the carbon source may include amorphous carbon, conductive carbon black, acetylene black, Ketjen black, furnace black, graphite, expanded graphite, graphene, graphene oxide, reduced graphene oxide, carbon nanotubes, carbon nanofibers, hard carbon, soft carbon, disordered layer carbon, porous carbon, mesoporous carbon, carbon quantum dots, and one or more of carbon doped with at least one heteroatom of N, B, P and S.
[0179] In some specific embodiments, the carbon source is one or more of conductive carbon black, acetylene black, Ketjen black, graphene, graphene oxide, reduced graphene oxide, carbon nanotubes, and amorphous carbon.
[0180] In step (3) of method one and / or step (4) of method two, the polymer source refers to a polymer source that is based on at least one of organic polymer chains, ladder polymer chains and organic cross-linking networks, and can undergo one or more structural transformations such as adsorption film formation, cyclization, cross-linking, dehydrogenation, dehalogenation, aromatization, oxidative stabilization and partial carbonization during heat treatment.
[0181] In step (3) of Method 1 and / or step (4) of Method 2, the polymer source may include one or more of the following: nitrile polymers, imide-containing polymers, fluoropolymers, acrylate polymers, polymers containing hydroxyl or ether bonds, nitrogen-containing heterocyclic polymers, aromatic thermosetting polymers, natural polymers and their derivatives.
[0182] Preferably, the nitrile polymer comprises one or more of polyacrylonitrile, partially cyclized polyacrylonitrile, and copolymers containing acrylonitrile structural units; the imide-containing polymer preferably comprises one or more of polyimide, polyamide-imide, and their precursors; the fluorinated polymer preferably comprises one or more of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, and polytetrafluoroethylene; the acrylate polymer preferably comprises one or more of polymethyl methacrylate, polyacrylic acid, polyacrylate, and their copolymers; the hydroxyl- or ether-containing polymer preferably comprises one or more of polyvinyl alcohol, polyethylene glycol, and polyethylene oxide; the nitrogen-containing heterocyclic polymer preferably comprises one or more of polyvinylpyrrolidone, polypyrrole, polyaniline, and polydopamine; the aromatic thermosetting polymer preferably comprises one or more of phenolic resin, epoxy resin, and furan resin; and the natural polymer and its derivatives preferably comprise one or more of cellulose, cellulose derivatives, chitosan, alginic acid, and alginate.
[0183] In some specific embodiments, the polymer source includes one or more of polyacrylonitrile, partially cyclized polyacrylonitrile, acrylonitrile copolymer, polyimide, polyamide-imide, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, and polymethyl methacrylate.
[0184] In step (3) of method one and / or step (4) of method two, the total amount of the coating material source added, based on the formation of the coating, is preferably 0.05%-10% of the mass of the lithium-based morphological oxide intermediate material.
[0185] In step (3) of method one and / or step (4) of method two, the mass of the coating material source as a percentage of the mass of the lithium-based layered oxide intermediate material is preferably 0.1%-10%, for example 0.3%, 0.5%, 0.6%, 0.87%, 0.9%, 1%, 1.1%, 1.2%, 1.5%, 1.56%, 2%, 3% or 5%.
[0186] In step (3) of Method 1 and / or step (4) of Method 2, the coating treatment can be one or more of liquid phase coating, dry coating, and vapor phase deposition coating. Preferably, the dry coating includes the following process: directly mixing the lithium-based layered oxide intermediate material with a solid coating material source without relying on the dissolution or dispersion of the coating material source in a continuous liquid medium, and then using one or more of mechanical force, shear force, impact force, friction force, and interparticle interaction to cause the coating material source to adhere, embed, or spread onto the outer surface of the particles.
[0187] In some specific embodiments, the dry coating includes the following process: mechanically fusing the lithium-based morphological oxide intermediate material with the coating material source, low-energy ball milling, airflow mixing, high-speed shear mixing, jet mixing, and roll pressing mixing, so that the coating material source adheres to the outer surface of the particles. Preferably, the dry coating does not involve the addition of a liquid medium, or only a small amount of liquid medium is added to improve particle wettability, dispersibility, or surface adhesion.
[0188] The vapor deposition coating refers to the process of delivering a gaseous coating material source and / or gaseous active species generated by the coating material source to the surface of the lithium-based crystalline oxide intermediate material, and forming a coating layer through adsorption, decomposition, chemical reaction, or layer-by-layer deposition. Preferably, the vapor deposition coating includes one or more of chemical vapor deposition, atomic layer deposition, physical vapor deposition, and molecular layer deposition.
[0189] Preferably, the liquid-phase coating includes the following process: dissolving, dispersing, or suspending the coating material source in a liquid medium, contacting the coating material source with the lithium-based layered oxide intermediate material, and subjecting it to one or more processes such as adsorption, deposition, precipitation, gelation, and solvent removal to distribute the coating material source onto the outer surface of the particles. The liquid-phase coating preferably includes one or more of the following: solution coating, impregnation coating, dispersion coating, sol-gel coating, precipitation coating, and spray coating. The liquid medium can be removed by one or more of the following methods: evaporation, filtration, centrifugation, spray drying, vacuum drying, and freeze drying.
[0190] The liquid phase coating preferably includes the following process: adding the lithium-based morphological oxide intermediate material to a dispersion containing a coating material source to obtain a mixture, and then subjecting the mixture to solvent evaporation and heat treatment.
[0191] The lithium-based morphological oxide intermediate material can be added in batches, for example, in 2-5 batches.
[0192] The solvent in the dispersion containing the coating material source can be conventional in the art, generally including at least one of deionized water, anhydrous ethanol, N,N-dimethylformamide, isopropanol, acetonitrile, and dimethyl sulfoxide. The mass concentration of the dispersion containing the coating material source can be (1-10) mg / mL, for example, 2 mg / mL, 2.5 mg / mL, 2.9 mg / mL, 3 mg / mL, 3.3 mg / mL, 3.5 mg / mL, 3.7 mg / mL, 4 mg / mL, 5.2 mg / mL, or 8 mg / mL.
[0193] The preparation method of the dispersion containing the coating material source may include the following steps: adding the coating material source to a solvent and mixing evenly. The mixing method can be conventional in the art, such as stirring and / or ultrasonication; the mixing temperature can be 20-70℃, for example 25℃, 30℃ or 50℃; the mixing time can be 10min-3h, for example 20min, 30min, 40min, 1h or 2h. During the mixing process, a dispersant may also be added; the dispersant can be conventional in the art, such as polyvinylpyrrolidone; the mass ratio of the dispersant to the volume of the solvent can be (0.1-2) mg / mL, for example 0.3 mg / mL, 0.67 mg / mL, 0.8 mg / mL or 1 mg / mL. When adding the dispersant, the solvent and dispersant can be mixed evenly first, and then the coating material source can be added.
[0194] According to conventional methods in the art, the solvent evaporation can be carried out using conventional methods, such as stirring evaporation under heating or vacuum evaporation. The evaporation is generally continued until no significant solvent remains. The evaporation temperature can be 50-80°C, for example, 60°C; the evaporation time can be 1-12 hours, for example, 2 hours or 6 hours.
[0195] After the solvent is evaporated and before the heat treatment, drying is generally required. The drying method is generally vacuum drying; the drying temperature can be 60-120℃, for example 70℃, 80℃ or 90℃; the drying time can be 6-24h, for example 8h or 12h.
[0196] The coating material source introduced by the aforementioned liquid phase coating, dry coating or vapor phase deposition coating can directly retain its original structure, or it can undergo one or more transformations such as decomposition, condensation, film formation, crystallization, amorphization, cyclization, crosslinking, aromatization or partial carbonization after subsequent drying, curing and heat treatment, thereby forming the functional coating layer.
[0197] In step (3) of method one and / or step (4) of method two, when the coating treatment is liquid phase coating or dry coating, it is preferable to perform heat treatment after the coating treatment; when the coating treatment is vapor phase deposition coating, it is generally not necessary to perform heat treatment after the coating treatment, and only drying or curing treatment is required.
[0198] The atmosphere for the heat treatment can be conventional in the art; when the coating material source is at least one of a solid electrolyte source, a polyanionic compound source, an inorganic glassy material source, an amorphous oxide source, and a metal oxide source, the atmosphere for the heat treatment can be air, oxygen, nitrogen, or argon, and the rate of heating to the heat treatment temperature is preferably 1-5°C / min, for example, 2°C / min; when the coating material source is a carbon source, the atmosphere for the heat treatment can be nitrogen or argon; when the coating material source is a polymer source, the atmosphere for the heat treatment can be air, and the rate of heating to the heat treatment temperature is preferably 0.2-2°C / min, for example, 0.5°C / min, 0.8°C / min, or 1°C / min.
[0199] The heat treatment temperature can be 100-500℃, preferably 150-500℃, for example 200℃, 250℃, 260℃, 280℃, 300℃, 350℃, 400℃, or 450℃; the heat treatment time is 0.2-12h, for example 0.5h, 1h, 1.5h, 2h, 4h, or 6h. Within this defined temperature range, the heat treatment can be used to remove solvents or temporary organic components, promote the adhesion, film formation, or in-situ transformation of the coating material, and prevent significant coarsening or rearrangement of the composite oxide reconstruction interface layer and the multilayered structural domains.
[0200] In this invention, relevant open-ended expressions can be modified to closed-ended expressions accordingly, for example, "including" can be modified to "is".
[0201] The present invention also provides a multiphase fast transport layered cathode material prepared by the preparation method described above.
[0202] The present invention also provides a battery comprising a positive electrode, a negative electrode and an electrolyte, wherein the positive electrode active layer on the positive electrode comprises the multiphase fast transport layered positive electrode material as described above.
[0203] In this invention, the multiphase fast-transport layered cathode material accounts for 60%-99.5% of the mass percentage of the cathode active layer. The cathode active layer generally also includes a conductive agent and a binder. The conductive agent may be one or more of carbon black, carbon nanotubes, graphene, and conductive fibers; the binder may be one or more of PVDF, PTFE, SBR, CMC, and PAA.
[0204] In this invention, the negative electrode active material on the negative electrode sheet can be graphite, silicon carbide, lithium metal, or lithium titanate.
[0205] In this invention, the electrolyte may be a liquid organic electrolyte, a gel electrolyte, a polymer electrolyte, a sulfide solid electrolyte, an oxide solid electrolyte, or a halide solid electrolyte.
[0206] The present invention also provides an application of the multiphase fast transport layered cathode material as described above in a battery.
[0207] In this invention, the battery is preferably a lithium-ion battery.
[0208] Based on common knowledge in the field, the above-mentioned preferred conditions can be combined arbitrarily to obtain various preferred embodiments of the present invention.
[0209] The reagents and raw materials used in this invention are all commercially available.
[0210] The positive and progressive effects of this invention are as follows:
[0211] (1) By pre-configuration and topological exchange of non-lithium alkali metal layered precursors, a multi-stacked structural domain cross-generation host sharing a transition metal-oxygen framework is obtained in the same particle or grain, avoiding limiting "multiphase" to macroscopic heterogeneous phase mixing;
[0212] (2) By utilizing different lithium coordination and stacking environments such as O3, O2, T2, and O6 and their cross-generation boundaries, a lithium-ion transport network with interlayer channels and boundary bypasses is constructed, and the charging and discharging stress is dispersed through layer slip, stacking faults, and micro-strain regions.
[0213] (3) The in-situ connection between the main multiphase structure and the surface reconstruction layer is beneficial to take into account high-rate ion transport, high voltage structural stability, suppression of interfacial side reactions and cycle life.
[0214] (4) The bulk multilayer domain and doping, the primary particle surface reconstruction layer and the outermost functional coating layer of the particle work together from the inside to the outside, which can take into account the rapid transport of bulk phase, gradual structural change, outer layer ion conduction, interface protection and suppress interface side reactions. Attached Figure Description
[0215] Figure 1 This is a schematic diagram of the three-layer hierarchical structure of the multiphase fast transport layered cathode material prepared in this invention;
[0216] Figure 2 The image shows the HAADF-STEM image of the bulk phase of the composite material prepared in step (2) of Example 1.
[0217] Figure 3 The image shows the HAADF-STEM image of the surface of the composite material prepared in step (2) of Example 1.
[0218] Figure 4 The image shows the HAADF-STEM image of the bulk phase of the composite material prepared in step (3) of Example 3;
[0219] Figure 5 The image shows the HAADF-STEM image of the surface of the composite material prepared in step (3) of Example 3.
[0220] Figure 6 The image shows a TEM image of the interface of the composite material prepared in step (3) of Example 1.
[0221] Figure 7 This is a TEM image of the cathode material prepared in Comparative Example 4;
[0222] Figure 8 Cycling curves of the composite material prepared in Example 2 and the lithium cobalt oxide prepared in Comparative Example 1 are shown.
[0223] Figure 9The graphs show the cycling curves of the composite materials prepared in Examples 3-4 and the high-nickel ternary material prepared in Comparative Example 3.
[0224] Figure 10 The XRD patterns are of the materials prepared in Examples 1-2; Figure 10 In this context, 'a' represents the P2 phase layered oxide precursor prepared in step (1) of Example 1; Figure 10 In this context, 'b' represents the T2 / O2 composite phase prepared in step (2) of Example 1; Figure 10 In this context, 'c' represents the O3 phase lithium cobalt oxide host material prepared in step (2) of Example 2.
[0225] Explanation of reference numerals in the attached figures: A lithium-based substrate oxide material containing multilayered structural domains and doped elements 1; Composite oxide reconstructed interface layer 2 formed on the surface of primary particles; 3. Functional coating layer located on the outermost side of particles or particle aggregates. Detailed Implementation
[0226] The present invention is further illustrated below by way of embodiments, but the invention is not limited to the scope of the embodiments described herein. Experimental methods in the following embodiments that do not specify specific conditions were performed according to conventional methods and conditions, or as selected according to the product instructions.
[0227] Example 1: Na-preformed T2 / O2 composite phase lithium cobalt oxide host material and interface construction
[0228] Step (1): Mix Co3O4, Na2CO3 and TiO2 according to Na 0.8 Co 0.99 Ti 0.01 The stoichiometric amount of O2 was measured, with Na2CO3 in 2% excess relative to the target amount. The above raw materials were then subjected to dry ball milling (400 rpm, 3 h, ball diameter 5 mm, ball-to-material ratio 10:1, without any solvent) and transferred to a tube furnace. The furnace was heated to 810 °C at a rate of 3 °C / min in an oxygen atmosphere and held for 10 h. After natural cooling to room temperature, the P2 phase layered oxide precursor Na was obtained. 0.8 Co 0.99 Ti 0.01 O2.
[0229] Step (2): The P2 phase layered oxide precursor, LiNO3, and CaCl2 were rapidly dry-milled in a mortar for 5 min at a Li / Na molar ratio of 5:1 and a Ca / (Co+Ti) molar percentage of 0.3 mol%. The mixture was then placed directly into a tube furnace preheated to 280℃ and held at this temperature for 20 min under an oxygen atmosphere. After the reaction was complete, the mixture was quickly removed and air-quenched. The product was washed with water until the filtrate was nearly neutral, and then vacuum-dried at 90℃ for 8 h to obtain the T2 / O2 composite phase lithium cobalt oxide (Li). 0.8 Co 0.99 Ti 0.01 O2@Ca-Ti-Co-O.
[0230] Step (3): Weigh 10.00 g of the material obtained in step (2) as an intermediate. Dissolve 64 mg LiNO3, 12 mg H3BO3 and 34 mg NH4H2PO4 in 1.5 mL of deionized water, then add 28.5 mL of anhydrous ethanol and stir to form a lithium boron phosphorus oxide precursor solution. Add the intermediate to the precursor solution, stir at 60 °C for 2 h and slowly evaporate the solvent, then vacuum dry at 80 °C for 8 h; subsequently, heat to 280 °C at 2 °C / min under an oxygen atmosphere and hold for 1 h, then naturally cool to obtain a three-layer hierarchical structure material with Li-BPO amorphous material as the main outermost layer. Based on the complete retention of Li, B, and P elements in LiNO3, H3BO3, and NH4H2PO4, and the theoretical calculation based on the existence of anhydrous and nitrogen-free Li-BPO inorganic amorphous network material, the theoretical mass of the resulting functional coating layer (Li2O, B2O3, P2O5) is approximately 41.6 mg, which is approximately 0.416% of the mass of the intermediate obtained in step (2). The theoretical mass does not include nitrogen-containing components, water, and other volatile components that escape during the heat treatment process.
[0231] Example 2: Bulk Ti Stabilization and Interface Construction of O3 Phase Lithium Cobalt Oxide
[0232] Step (1): Mix Na2CO3, Co3O4 and TiO2 according to Na 1.04 Co 0.99 Ti 0.01 The stoichiometric composition of O2 was weighed, with Na2CO3 in 2% excess relative to the target. The above raw materials were then subjected to dry ball milling (400 rpm, 3 h, ball diameter 5 mm, ball-to-material ratio 10:1, without any solvent) and transferred to a tube furnace. The temperature was increased to 835 °C at a rate of 3 °C / min in an oxygen atmosphere and held for 5 h. After natural cooling to room temperature, the P2 phase Ti pre-doped Na-based basal oxide precursor Na was obtained. 1.04 Co 0.99 Ti 0.01 O2.
[0233] Step (2): The precursor and LiNO3 were dry-ground and mixed in a mortar at a Li / Na molar ratio of 5:1 for 5 min. The mixture was then placed directly into a tube furnace preheated to 385℃ and kept at this temperature for 4 h under an oxygen atmosphere to process the LiNO3 mixture. + / Na + Topological exchange was performed, and the product was rapidly removed and air-quenched after the reaction. The product was washed with water until the filtrate was nearly neutral, and then vacuum-dried at 90°C for 8 h to obtain the O3 phase lithium cobalt oxide host material LiCo. 0.99 Ti 0.01 O2.
[0234] Step (3): The O3 phase lithium cobalt oxide host material, Li2CO3, and CaCO3 were dry ball-milled (400 rpm, 3 h, ball diameter 5 mm, ball-to-material ratio 10:1, without any solvent). The lithium element in Li2CO3 was 5% of the molar fraction of the lithium cobalt oxide host material; the molar percentage of Ca in the calcium source and Co and Ti in the lithium cobalt oxide host material, i.e., Ca / (Co+Ti), was 1.0 mol%. The mixed powder was transferred to a tube furnace and heated to 650℃ in oxygen at a heating rate of 3℃ / min and held for 3 h. After natural cooling to room temperature, LiCo was obtained. 0.99 Ti 0.01 O2@Ca-Ti-Co-O.
[0235] Step (4): Weigh 10.00 g of the material obtained in step (3) as an intermediate. Dissolve 64 mg LiNO3, 12 mg H3BO3 and 34 mg NH4H2PO4 in 1.5 mL of deionized water, then add 28.5 mL of anhydrous ethanol and stir to form a lithium boron phosphorus oxide precursor solution. Add the intermediate to the solution, stir at 60 °C for 2 h and slowly evaporate the solvent, then vacuum dry at 80 °C for 8 h; subsequently, heat to 280 °C at 2 °C / min under an oxygen atmosphere and hold for 1 h, then cool naturally to obtain a three-layer hierarchical structure material with Li-BPO amorphous material as the main outermost layer.
[0236] Example 3: Construction of Na-preformed high-nickel ternary layered cathode and interface
[0237] Step (1): Mix Na2CO3, NiO, Co3O4, MnO2, TiO2, and MoO3 according to Na 0.9 [Ni 0.8 Co 0.1 Mn 0.1 ] 0.99 Ti 0.005 Mo 0.005The stoichiometric ratio of O2 was determined, with Na2CO3 in 2% excess relative to the target. All powders were dry-ball-milled (400 rpm, 3 h, ball diameter 5 mm, ball-to-powder ratio 10:1, without any solvent), then transferred to a tube furnace. The furnace was heated to 700 °C at a rate of 3 °C / min and held for 5 h in an oxygen atmosphere. After natural cooling to room temperature, the Ti / Mo pre-doped P2 phase Na / K layered high-nickel oxide precursor Na was obtained. 0.9 [Ni 0.8 Co 0.1 Mn 0.1 ] 0.99 Ti 0.005 Mo 0.005 O2.
[0238] Step (2): The precursor and LiCl were dry-milled and mixed in a mortar at a Li / Na molar ratio of 5:1 for 5 min. The mixture was then placed directly into a tube furnace preheated to 650℃ and kept at this temperature for 5 h under an oxygen atmosphere for topological exchange. After the reaction was complete, the mixture was quickly removed and air-quenched. The product was washed with water until the filtrate was nearly neutral and then vacuum-dried at 90℃ for 8 h to obtain the O3 phase host material, Li. 0.9 [Ni 0.8 Co 0.1 Mn 0.1 ] 0.99 Ti 0.005 Mo 0.005 O2.
[0239] Step (3): The main material, Li2CO3, and La2O3 were dry-milled (400 rpm, 3 h, ball diameter 5 mm, ball-to-material ratio 10:1, without any solvent). The lithium element in Li2CO3 was 15% of the molar amount of the main material; the La element in La2O3 was 0.3% of the molar amount of non-lithium metal elements in the main material. The mixed powder was transferred to a tube furnace and heated to 500℃ in oxygen at a heating rate of 3℃ / min and held for 5 h. Then, without cooling, the temperature was increased to 750℃ at a heating rate of 3℃ / min and held for 5 h. After natural cooling to room temperature, Li[Ni] was obtained. 0.8 Co 0.1 Mn 0.1 ] 0.99 Ti 0.005 Mo 0.005 O2@La-TM-O.
[0240] Step (4): Weigh 10.00 g of the material obtained in step (3) as an intermediate. Dissolve 64 mg LiNO3, 12 mg H3BO3 and 34 mg NH4H2PO4 in 1.5 mL of deionized water, then add 28.5 mL of anhydrous ethanol and stir to form a lithium boron phosphorus oxide precursor solution. Add the intermediate to the solution, stir at 60 °C for 2 h and slowly evaporate the solvent, then vacuum dry at 80 °C for 8 h; subsequently, heat to 280 °C at 2 °C / min under an oxygen atmosphere and hold for 1 h, then cool naturally to obtain a three-layer hierarchical structure material with Li-BPO amorphous material as the main outermost layer.
[0241] Example 4: Construction of a high-nickel ternary layered cathode with Na / K co-preformation and its interface
[0242] Step (1): Mix NiO, Co3O4, MnO2, Na2CO3, K2CO3, TiO2, and MoO3 according to Na 0.86 K 0.04 [Ni 0.8 Co 0.1 Mn 0.1 ] 0.99 Ti 0.005 Mo 0.005 The stoichiometric ratio of O2 was determined, with Na2CO3 and K2CO3 each in 2% excess relative to the target stoichiometry. All powders were dry-ball-milled (400 rpm, 3 h, ball diameter 5 mm, ball-to-powder ratio 10:1, without any solvent), then transferred to a tube furnace. The furnace was heated to 700 °C at a rate of 3 °C / min in an oxygen atmosphere and held for 5 h. After natural cooling to room temperature, the precursor Na was obtained. 0.86 K 0.04 [Ni 0.8 Co 0.1 Mn 0.1 ] 0.99 Ti 0.005 Mo 0.005 O2.
[0243] Steps (2)-(4): Same as in Example 3.
[0244] Example 5
[0245] Compared with Example 1, except that CaCl2 in step (2) is replaced with BaCl2, all other operations and conditions are the same as in Example 1.
[0246] Example 6
[0247] Compared with Example 1, except that the molar percentage of CaCl2 in step (2) is adjusted to 0.1 mol%, all other operations and conditions are the same as in Example 1.
[0248] Example 7
[0249] Compared with Example 1, except that the molar percentage of CaCl2 in step (2) is adjusted to 1 mol%, all other operations and conditions are the same as in Example 1.
[0250] Example 8
[0251] Compared with Example 1, except that the calcination temperature in step (2) is adjusted to 260°C, all other operations and conditions are the same as in Example 1.
[0252] Example 9
[0253] Compared with Example 1, except that the calcination temperature in step (2) is adjusted to 300°C, all other operations and conditions are the same as in Example 1.
[0254] Example 10
[0255] Compared with Example 1, except that the calcination time in step (2) is adjusted to 2 hours, all other operations and conditions are the same as in Example 1.
[0256] Example 11
[0257] Compared with Example 1, except that the amount of HBO3 in step (3) was adjusted to 24 mg and the amount of NH4H2PO4 was adjusted to 68 mg, the other operations and conditions were the same as in Example 1.
[0258] Example 12
[0259] Compared with Example 1, except that the amount of HBO3 in step (3) was adjusted to 6 mg and the amount of NH4H2PO4 was adjusted to 17 mg, the other operations and conditions were the same as in Example 1.
[0260] Example 13
[0261] Compared with Example 3, except that in step (1) Na2CO3, NiO, Co3O4, MnO2, TiO2 and Nb2O5 are added according to Na 0.9 [Ni 0.8 Co 0.1 Mn 0.1 ] 0.99 Ti 0.005 Nb 0.005 Except for the stoichiometric weighing of O2, all other operations and conditions are the same as in Example 3.
[0262] Example 14
[0263] Compared with Example 3, except that the raw materials in step (1) are prepared according to Na 0.9 [Ni0.8 Co 0.1 Mn 0.1 ] 0.996 Ti 0.002 Mo 0.002 Except for the stoichiometric weighing of O2, all other operations and conditions are the same as in Example 3.
[0264] Example 15
[0265] Compared with Example 3, except that the raw materials in step (1) are prepared according to Na 0.9 [Ni 0.8 Co 0.1 Mn 0.1 ] 0.98 Ti 0.01 Mo 0.01 Except for the stoichiometric weighing of O2, all other operations and conditions are the same as in Example 3.
[0266] Example 16
[0267] Compared with Example 3, except that the calcination temperature in step (1) is adjusted to 600°C, all other operations and conditions are the same as in Example 3.
[0268] Example 17
[0269] Compared with Example 3, except that the calcination temperature in step (1) is adjusted to 800°C, all other operations and conditions are the same as in Example 3.
[0270] Example 18
[0271] Compared with Example 3, except that the calcination time in step (1) is adjusted to 2h, the other operations and conditions are the same as in Example 3.
[0272] Example 19
[0273] Compared with Example 3, except that the calcination temperature in step (2) is adjusted to 700°C, all other operations and conditions are the same as in Example 3.
[0274] Example 20
[0275] Compared with Example 3, except that the calcination time in step (2) is adjusted to 3h, the other operations and conditions are the same as in Example 3.
[0276] Example 21
[0277] Compared with Example 3, except that La2O3 in step (3) is replaced with CaCO3, all other operations and conditions are the same as in Example 3.
[0278] Example 22
[0279] Compared with Example 3, except that the amount of La element added in La2O3 in step (3) is adjusted to 0.1%, all other operations and conditions are the same as in Example 3.
[0280] Example 23
[0281] Compared with Example 3, except that the amount of La element added in La2O3 in step (3) is adjusted to 0.5%, all other operations and conditions are the same as in Example 3.
[0282] Example 24
[0283] Compared with Example 3, except that the two-step annealing in step (3) is changed to a one-step method, the other operations and conditions are the same as in Example 3: the mixed powder is transferred to a tube furnace and heated to 750°C in oxygen at a heating rate of 3°C / min and held for 5 hours. The other operations and conditions are the same as in Example 3.
[0284] Example 25
[0285] Compared with Example 3, except that the amount of HBO3 in step (4) was adjusted to 24 mg and the amount of NH4H2PO4 was adjusted to 68 mg, the other operations and conditions were the same as in Example 1.
[0286] Example 26
[0287] Compared with Example 3, except that the amount of HBO3 in step (4) was adjusted to 6 mg and the amount of NH4H2PO4 was adjusted to 17 mg, the other operations and conditions were the same as in Example 1.
[0288] Example 27: Preparation of K-pre-structured Ti-doped lithium-rich manganese-based substrate cathode material
[0289] Step (1): Containing Ti 4+ Preparation of sodium-based layered oxide precursors
[0290] K2CO3, Li2CO3, NiO, Co3O4, MnO2, and TiO2 were added according to the target product K. 0.8 Li 0.2 Ni 0.132 Co 0.132 Mn 0.53 Ti 0.006The stoichiometric ratio of O2 was measured. The theoretical molar ratio of K2CO3, Li2CO3, NiO, Co3O4, MnO2, and TiO2 was 0.4:0.1:0.132:0.044:0.53:0.006. Na2CO3 and Li2CO3 were added in excess by 3% based on the theoretical amount to compensate for the loss of sodium and lithium volatilization during the high-temperature heat treatment.
[0291] The above raw materials were subjected to dry ball milling at 400 rpm for 3 hours. The ball diameter was 5 mm, and the ball-to-material ratio was 10:1. No solvent was added during the ball milling process. The milled powder was transferred to a tube furnace and pre-sintered at 600 °C from room temperature at a heating rate of 5 °C / min under an oxygen atmosphere for 4 hours. Subsequently, the temperature was further increased to 900 °C and held for 12 hours. After natural cooling to room temperature, Ti-containing P2 phase was obtained. 4+ Sodium-based layered oxide precursor, with the nominal chemical formula K 0.8 Li 0.2 Ni 0.132 Co 0.132 Mn 0.53 Ti 0.006 O2.
[0292] Step (2): Li + / K + Construction of Topology Switching and Ca-Ti-TM-O Reconstruction Interface Layer
[0293] Weigh 0.5 g of the Ti-containing sample obtained in step (1). 4+ A sodium-based crystalline oxide precursor was added to an agate mortar along with a eutectic lithium salt composed of LiNO3 and LiCl, and CaCO3, and rapidly dry-milled for 5 min. The molar ratio of LiNO3 to LiCl in the eutectic lithium salt was 88:12, and the molar ratio of the sodium-based crystalline oxide precursor to the total eutectic lithium salt was 1:2. The amount of CaCO3 added was determined according to the ratio of Ca to the total molar amounts of Ni, Co, Mn, and Ti in the precursor, with Ca / (Ni+Co+Mn+Ti) being 1.0 mol.
[0294] The resulting mixture was placed directly into a tube furnace preheated to 285 °C and held at that temperature for 4 h under an oxygen atmosphere to allow the eutectic lithium salt to form a liquid phase and undergo Li + / Na + Topological exchange. After the reaction was complete, the reaction product was quickly removed and air-quenched. The quenched product was repeatedly washed with deionized water to remove residual LiNO3, LiCl, and soluble sodium salts formed during the ion exchange process, until the filtrate was nearly neutral; then it was vacuum-dried at 90 °C for 8 h.
[0295] Step (3): Weigh 10.00 g of the material obtained in step (2) as an intermediate. Dissolve 64 mg LiNO3, 12 mg H3BO3 and 34 mg NH4H2PO4 in 1.5 mL of deionized water, then add 28.5 mL of anhydrous ethanol and stir to form a lithium boron phosphorus oxide precursor solution. Add the intermediate to the solution, stir at 60 °C for 2 h and slowly evaporate the solvent, then vacuum dry at 80 °C for 8 h; subsequently, heat to 280 °C at 2 °C / min under an oxygen atmosphere and hold for 1 h, then cool naturally to obtain a three-layer hierarchical structure material with Li-BPO amorphous material as the main outermost layer.
[0296] Example 28
[0297] Steps (1)-(2): Same as in Example 27;
[0298] Step (3): Weigh 10.00 g of the material obtained in step (2) as an intermediate. Add 100 mg Li 6.4 La3Zr 1.4 Ta 0.6 O 12 LLZTO oxide solid electrolyte powder was added to 30 mL of anhydrous ethanol, along with 20 mg of polyvinylpyrrolidone as a temporary dispersant. The mixture was ultrasonically dispersed for 30 min to obtain an LLZTO dispersion. An intermediate was added to the LLZTO dispersion, and the mixture was stirred at 60 °C for 2 h while the solvent was slowly evaporated simultaneously until a uniform wet powder was formed. Subsequently, the powder was vacuum dried at 80 °C for 8 h. The dried powder was placed in a tube furnace and heated to 300 °C at a rate of 2 °C / min under an oxygen atmosphere and held for 1 h. After natural cooling, a three-layered structure material with an outermost LLZTO oxide solid electrolyte coating was obtained.
[0299] Example 29
[0300] Steps (1)-(2): Same as in Example 27;
[0301] Step (3): Weigh 10.00 g of the material obtained in step (2) as an intermediate. Add 100 mg of polyacrylonitrile (PAN) with a weight average molecular weight of approximately 150,000 to 30 mL of anhydrous N,N-dimethylformamide and stir at 50 °C for 2 h until the polyacrylonitrile is fully dissolved to obtain a polyacrylonitrile coating solution. Add the intermediate to the polyacrylonitrile coating solution in three batches, disperse ultrasonically for 10 min, and then continue stirring at 50 °C for 8 h to allow the polyacrylonitrile to be fully adsorbed onto the surface of the intermediate particles. Evaporate the solvent in the resulting mixture under reduced pressure at 60 °C until a uniform powder is formed; then vacuum dry at 80 °C for 12 h to remove residual solvent. Place the dried powder in a tube furnace, heat it to 260 °C at a rate of 0.5 °C / min in air atmosphere and hold for 30 min, then cool naturally to obtain a three-layer hierarchical structure material with a partially cyclized and cross-linked polyacrylonitrile-derived ladder-shaped nitrogen-containing organic polymer coating layer as the outermost layer. Low heating rates and short heat treatment times are used to promote partial cyclization and cross-linking of polyacrylonitrile (PAI) molecular chains, forming heat-treated convertible organic polymers with ladder-like or quasi-ladder-like chain segments. This improves the bonding stability between the functional coating layer and the composite oxide reconstructed interface layer, and inhibits the further conversion of PAI into carbonaceous materials with a carbon skeleton. The actual mass of the functional coating layer can be calculated or determined based on the loading rate of PAI on the intermediate surface and its solid mass retention rate under the same heat treatment conditions.
[0302] Example 30
[0303] Compared with Example 29, except that the amount of polyacrylonitrile in step (3) is adjusted to 50 mg, all other operations and conditions are the same as in Example 29.
[0304] Example 31
[0305] Compared with Example 29, except that the amount of polyacrylonitrile in step (3) is adjusted to 150 mg, all other operations and conditions are the same as in Example 29.
[0306] Example 32
[0307] Steps (1)-(2): Same as in Example 27;
[0308] Step (3): Weigh 10.00 g of the material obtained in step (2) as an intermediate. Add 100 mg of γ-Al2O3 metal oxide powder to 30 mL of anhydrous ethanol, and simultaneously add 20 mg of polyvinylpyrrolidone as a temporary dispersant. Disperse ultrasonically for 30 min to obtain a γ-Al2O3 dispersion. Add the intermediate to the γ-Al2O3 dispersion in batches, disperse ultrasonically for 10 min, and then stir at 60℃ for 2 h while simultaneously evaporating the solvent slowly to allow the γ-Al2O3 particles to be uniformly adsorbed on the surface of the intermediate particles until a uniform wet powder is formed. Then, vacuum dry at 80℃ for 8 h to remove residual solvent. Place the dried powder in a tube furnace, heat it to 400℃ at 2℃ / min under an oxygen atmosphere and hold for 2 h, then cool naturally to obtain a three-layer hierarchical structure material with a γ-Al2O3 metal oxide coating layer as the outermost layer.
[0309] Example 33
[0310] Steps (1)-(2): Same as in Example 27;
[0311] Step (3): Weigh 10.00 g of the material obtained in step (2) as an intermediate. Add 100 mg of lithium orthophosphate (Li3PO4) polyanionic compound to 30 mL of anhydrous ethanol and stir to form a precursor solution. Add the intermediate to the solution, stir at 60 °C for 2 h and slowly evaporate the solvent, and dry under vacuum at 80 °C for 8 h; then heat to 280 °C at 2 °C / min under an oxygen atmosphere and hold for 1 h, and cool naturally to obtain a three-layer hierarchical structure material.
[0312] Example 34
[0313] Steps (1)-(2): Same as in Example 27;
[0314] Step (3): Weigh 10.00 g of the material obtained in step (2) as an intermediate. Add 100 mg of graphene oxide to 30 mL of anhydrous ethanol and stir to form a precursor solution. Add the intermediate to the solution, stir at 60 °C for 2 h and slowly evaporate the solvent, and dry under vacuum at 80 °C for 8 h; then heat to 280 °C at 2 °C / min under argon atmosphere and hold for 1 h, and cool naturally to obtain a three-layer hierarchical structure material.
[0315] Example 35
[0316] Steps (1)-(2): Same as in Example 27;
[0317] Step (3): Weigh 10.00 g of the material obtained in step (2) as an intermediate. Add 100 mg of amorphous SiO2 to 30 mL of anhydrous ethanol and stir to form a precursor solution. Add the intermediate to the solution, stir at 60 °C for 2 h and slowly evaporate the solvent, and vacuum dry at 80 °C for 8 h; then heat to 280 °C at 2 °C / min under an oxygen atmosphere and hold for 1 h, and cool naturally to obtain a three-layer hierarchical structure material.
[0318] Comparative Example 1: Direct lithiation of solid phase to prepare conventional O3 phase lithium cobalt oxide
[0319] Co3O4 and Li2CO3 were weighed according to the stoichiometric ratio of LiCoO2, with lithium carbonate in 5% excess relative to the target amount. The above raw materials were dry-ground and then transferred to a tube furnace, heated to 950℃ at a heating rate of 3℃ / min in an oxygen atmosphere and held for 20h to obtain O3 phase lithium cobalt oxide.
[0320] Comparative Example 2: No surface reconstruction layer constructed
[0321] Compared with Example 1, except that CaCl2 is not added in step (2), all other operations and conditions are the same as in Example 1.
[0322] Comparative Example 3: Preparation of high-nickel ternary materials by direct lithiation using co-precipitation precursors
[0323] Ni 0.8 Co 0.1 Mn 0.1 After the (OH)2 multi-component coprecipitation precursor was directly ground and mixed with LiOH, the molar ratio of Li:(Ni+Co+Mn) was 1.03:1. Conventional high-temperature sintering was carried out in oxygen, that is, preheating at 500℃ for 5h and then continuing to heat to 760℃ and holding for 10h.
[0324] Comparative Example 4
[0325] Step (1): Ni 0.8 Co 0.1 Mn 0.1 After directly grinding and mixing the (OH)2 multi-component coprecipitation precursor with LiOH, the molar ratio of Li:(Ni+Co+Mn) was 1.03:1. Conventional high-temperature sintering was then performed in oxygen, first preheating at 500℃ for 5 hours, then further heating to 760℃ and holding for 10 hours to obtain the ternary cathode material LiNi. 0.8 Co 0.1 Mn 0.1 O2.
[0326] Step (2): The ternary cathode material obtained in step (1) was ball-milled with perovskite oxide LaCoO3 at a molar ratio of 1:0.003 (400 rpm, 3 h, ball diameter 5 mm, ball-to-material ratio 10:1, without any solvent). The mixture was then heated to 650 °C in oxygen at a heating rate of 3 °C / min and held for 3 h to obtain LiNi. 0.8 Co 0.1 Mn 0.1 O2@LaCoO3.
[0327] Comparative Example 5: Preparation of lithium-rich manganese-based materials by direct lithiation using co-precipitation precursors
[0328] Ni 0.167 Co 0.167 Mn 0.667 (CO)3 multi-component coprecipitation precursor reacts with LiOH according to the target product Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 After O2 is directly ground and mixed, it is sintered at conventional high temperature, that is, preheated at 500℃ for 5 hours, and then the temperature is raised to 900℃ and held for 12 hours.
[0329] Comparative Example 6
[0330] Compared with Example 3, except that step (4) is not performed, everything else is the same as Example 3.
[0331] Effect Example
[0332] (1) Figure 1 This is a schematic diagram of the three-layer hierarchical structure of the multiphase fast transport layered cathode material prepared in this invention, showing the composite oxide reconstructed interface layer 2 formed on the surface of the lithium-based layered oxide host material 1 containing multilayer structural domains and doped elements, and the functional coating layer 3 located on the outermost side of the particles or particle agglomerates.
[0333] (2) TEM and XRD characterization
[0334] Figure 2 The composite material obtained in Example 1 exhibits a continuous layered transition metal-oxygen framework, along with lateral displacement of atomic layers along the layers, local layer bending, orientation changes, and stacking periodic perturbations. These characteristics indicate that the main body is not a simple mixture of separate macroscopic crystalline phases, but rather forms T2 domains, O2 domains, and their nanoscale intercalation transition regions within the same grain. Stacking transitions between the T2 and O2 domains are achieved through relative translation of the transition metal-oxygen layers. The transition boundaries may be accompanied by stacking faults, stacking mismatches, lattice microstrain, and local interlayer spacing changes, but the overall transition metal-oxygen layer remains continuous, consistent with the characteristics of framework inheritance and local layer slip synergistically forming a multiphase intercalation structure during topological exchange.
[0335] Figure 3 In the study, a surface reconstruction region with a thickness of approximately 10 nm and different atomic arrangement and contrast from the main body was observed on the outer side of the layered lithium cobalt oxide host. This region is continuously or quasi-continuously distributed along the particle surface. The long-range ordered layered arrangement inside the host gradually transforms into a locally short-range ordered reconstruction arrangement with a lower degree of long-range order near the surface, locally exhibiting short-range ordered characteristics consistent with rock salt-type reconstruction structures. No obvious pores, cracks, or independent particle separations were observed in the interface region, indicating that the surface reconstruction region and the layered lithium cobalt oxide host are bonded to each other through direct continuous contact and gradual structural change. Combined with the preparation process in Example 1, in which the Ca source, Ti-containing layered precursor, and lithium source are subjected to ion exchange thermal treatment, this surface region can be presumed to be a Ca-Ti-Co-O composite oxide reconstruction interface layer formed in situ by the Ca source participating in the local structural rearrangement of Ti and Co elements near the host surface.
[0336] Figure 4 The results show that the high-nickel layered matrix obtained in Example 3 has a relatively regular arrangement of transition metal atomic layers, and exhibits low-contrast defect bands extending along the layers, atomic pillar position shifts, and stacking period variations in local areas. This indicates that the matrix as a whole is dominated by an O3-type layered structure, with O3-type structural domains with different local layered lattice orientations existing within the same grain, as well as defect layered structural domains and their intergrowth boundaries formed by interlayer relative translation and stacking period perturbations. These intergrowth boundaries introduce local stacking faults and lattice micro-strain while maintaining the continuity of the matrix's layered framework.
[0337] Figure 5 In the high-nickel layered host, a La-TM-O composite reconstructed interface layer with a thickness of approximately 6 nm, extending with the curvature of the particle surface, can be observed on the outer side. This interface layer retains a certain local lattice contrast, but its overall long-range order is lower than that of the host, and it exhibits a composite reconstructed characteristic of coexistence of locally short-range ordered units and low-crystallinity regions, with local atomic arrangements consistent with rock salt-type reconstructed structures. From the interior of the host to the outer surface of the particles, the degree of order of the layered lattice and the atomic column contrast gradually change, and no obvious pores, cracks, or independent particle separations are observed at the interface, indicating that the host layered structure and the surface reconstructed region are bonded through direct continuous contact, local lattice connection, and gradual structural change. Combined with the preparation process of La2O3 and the high-nickel layered host being heat-treated together in Example 3, this surface region can be presumed to be a La-TM-O composite oxide reconstructed interface layer formed by in-situ reaction and local structural rearrangement of La with Ni, Co, and / or Mn near the host surface.
[0338] Figure 6The TEM image of the composite material interface prepared in step (3) of Example 1 shows that relatively continuous and regular lattice stripes can be seen inside the particles; as they approach the surface, the lattice stripes become significantly weaker, bent and interrupted, and lack long-range periodicity in some areas; there is a disordered layer of about 10 nm with low crystallinity / partial amorphization on the surface.
[0339] Figure 7 The material obtained in Comparative Example 4 exhibits a relatively uniform layered lattice arrangement within the observed region. The lattice fringes are generally continuous, straight, and nearly parallel, with no significant changes in interlayer spacing and stacking period. No features described in the examples, such as lateral displacement of atomic layers, local layer bending, lattice orientation rotation, stacking period perturbation, low-contrast defect bands, or atomic column misalignment, were observed. No distinguishable domain-intercalation boundaries, stacking fault-rich regions, or significant lattice microstrain were observed between different regions, indicating that the material mainly exhibits a single and uniform layered structure within the observed region, rather than forming a multiphase structure composed of intercalated different layered domains.
[0340] Figure 10 The images show the XRD patterns of the materials prepared in Examples 1-2.
[0341] (3) Electrochemical performance testing
[0342] 1. Preparation of lithium battery positive electrode sheet
[0343] The materials prepared in each embodiment and comparative example were used as positive electrode active materials, and were weighed and mixed evenly with conductive carbon black (Super P) and binder polyvinylidene fluoride (PVDF) at a mass ratio of 80:10:10. Subsequently, N-methylpyrrolidone (NMP) solvent, which was 2.5 times its total mass, was added to the mixed powder, and the resulting mixture was placed in a vortex mixer and stirred continuously at room temperature for 2 hours to form a uniform slurry.
[0344] The above slurry was uniformly coated onto a carbon-coated aluminum foil current collector. After drying in a forced-air oven at 110°C for 30 minutes, the electrode sheet was rolled and cut using a punching machine to obtain a circular positive electrode sheet with a diameter of 12 mm. This electrode sheet was then placed in a vacuum oven and dried at 110°C for 12 hours to completely remove residual solvent. The areal density of the active material on the resulting electrode sheet was approximately 2.0 mg / cm³. 2 After drying, the prepared electrode sheets are immediately transferred to an argon-filled glove box for battery assembly.
[0345] 2. Assembly of button-type lithium-ion batteries
[0346] CR2032 button cells were assembled in an argon atmosphere glove box with both moisture and oxygen concentrations below 0.1 ppm. All cell components (including cell casings, separators, and electrode plates) were ultrasonically cleaned and dried with ethanol before being transferred to the glove box.
[0347] The battery uses the positive electrode sheet prepared above as the positive electrode, the lithium metal sheet as the negative electrode, the separator as a ceramic separator (2ccs+12pe+2ccs), and the electrolyte as a mixed solution of 1 M lithium hexafluorophosphate (LiPF6) dimethyl carbonate (DMC) / ethylene carbonate (EC) / ethyl methyl carbonate (EMC) + 5 wt% fluoroethylene carbonate (FEC) (the volume ratio of solvent DMC:EC:EMC is 1:1:1, and FEC accounts for 5% of the total mass of the mixed solution).
[0348] The assembly sequence is as follows: place the negative electrode shell, lithium negative electrode, appropriate amount of electrolyte, separator, appropriate amount of electrolyte, positive electrode, and positive electrode shell in sequence. Ensure that the separator is fully wetted by the electrolyte and completely covers the electrode plates for effective isolation. After aligning the positive and negative electrode plates, seal them using an electric button battery sealing machine under a constant pressure of 700 kg.
[0349] The assembled batteries need to be allowed to mature for 6 hours before testing. The electrochemical performance test results are shown in Tables 1-3 and... Figures 8-9 The 1C value is 200 mA / g, and the test temperature is 25℃.
[0350] Table 1
[0351]
[0352] Note: "Not measured" means that no test has been conducted yet.
[0353] Table 2
[0354]
[0355] Note: Considering the intrinsic properties of manganese-based cathode materials, the rate range for rate testing of lithium-rich manganese-based cathodes is from 0.1C to 5C.
[0356] As shown in Tables 1 and 2, the multiphase fast-transport layered cathode material prepared in this invention exhibits excellent electrochemical performance, particularly high capacity, high rate capability, and high voltage structural stability. Figures 8-9 As shown in Table 3, the multiphase fast transport layered cathode material prepared in this invention has better cycle stability.
[0357] Table 3
[0358]
[0359] While specific embodiments of the present invention have been described above, those skilled in the art should understand that these are merely illustrative examples, and the scope of protection of the present invention is defined by the appended claims. Those skilled in the art can make various changes or modifications to these embodiments without departing from the principles and essence of the present invention, but all such changes and modifications fall within the scope of protection of the present invention.
Claims
1. A multiphase fast-transport layered cathode material, characterized in that, It includes a lithium-based morphological oxide host material, a composite oxide reconstruction interface layer located on the surface of the lithium-based morphological oxide host material, and a functional coating layer located on the surface of the composite oxide reconstruction interface layer. The lithium-based layered oxide host material includes at least two types of layered structural domains, and each layered structural domain has at least one different feature among the oxygen layer stacking sequence, interlayer translation relationship, cell repeating period, lithium ion coordination environment and local layered lattice orientation. The composite oxide reconstructed interface layer includes one or more of the following: electrochemically stable layered structure, spinel structure, rock salt structure, perovskite oxide structure, perovskite-like oxide structure, the aforementioned corresponding low crystallinity structure, and amorphous structure. The composite oxide reconstructed interface layer is in situ bonded to the surface of the lithium-based morphological oxide host material through one or more of the following methods: shared oxygen framework, element interdiffusion, local lattice connection, structural gradation and compositional gradient. The functional coating layer includes one or more of the following: solid electrolyte materials, compounds containing polyanionic structural units, inorganic glassy materials, amorphous oxides, metal oxides, carbonaceous materials, and heat-treated convertible organic polymer materials.
2. The multiphase fast-transport layered cathode material as described in claim 1, characterized in that, The multiphase fast-transport layered cathode material satisfies one or more of the following conditions: (1) The layered structural domains in the lithium-based layered oxide host material are distributed in a lamellar, strip, block, periodic alternating or non-periodic mismatched manner, and their characteristic scale is from a single or multiple transition metal-oxygen layers to tens of nanometers. (2) In the layered structural domains of the lithium-based layered oxide host material, adjacent layered structural domains share or continuously inherit the transition metal-oxygen framework; (3) In the layered structure domain of the lithium-based layered oxide host material, the transition between adjacent layered structure domains is achieved through one or more of the following methods: relative translation of adjacent transition metal-oxygen layers along the ab plane, layer tilting, in-plane orientation rotation, and change of oxygen layer stacking order. (4) In the layered structure domain of the lithium-based layered oxide host material, the transition boundary between adjacent layered structure domains is accompanied by one or more of the following: stacking faults, stacking mismatches, twins, dislocations, interlayer spacing expansion, lattice bending and lattice microstrain, but it is not required that the transition metal-oxygen framework completely breaks or re-nucleates. (5) The transition boundary between the layered structural domain and its adjacent layered structural domain forms a continuous or partially connected fast transmission region within the main body; (6) The structural type of the layered structural domain is selected from one or more of O3, O2, T2, O6 and their distorted structures; (7) The composite oxide reconstructed interface layer has an independent coating of a single long-range ordered crystalline phase or a composite reconstructed region formed by the intergrowth of multiple local coordination units; (8) The composite oxide reconstructed interface layer is manifested as one or more of the following: continuous layer, discontinuous island layer, dot-like enrichment region, grain boundary enrichment layer, or composition and structure gradient layer that gradually changes from the host to the outer surface; (9) The composite oxide reconstructed interface layer and the lithium-based morphological oxide host material form one or more of the following: structural continuity region, composition transition region and defect enrichment region, rather than forming a mechanical contact interface with a complete abrupt change in composition and structure and generated only by physical adhesion. (10) The functional coating layer is at least one of a continuous layer, a quasi-continuous layer, a mesh layer, and an island-connected layer; (11) The functional coating layer is located outside the composite oxide reconstructed interface layer and is in direct contact with it; (12) The functional coating layer and the composite oxide reconstructed interface layer are combined by at least one of physical bonding, chemical bonding, local element interdiffusion, and amorphous phase wetting; (13) The coating material in the functional coating layer exists in at least one of the following forms: particulate phase, continuous phase, short-range ordered phase, amorphous phase and interpenetrating network; (14) The thickness of the functional coating layer is 0.5-100 nm; (15) The mass percentage of the functional coating layer is 0.05%-10%.
3. The multiphase fast-transport layered cathode material as described in claim 1, characterized in that, The multiphase fast-transport layered cathode material satisfies one or more of the following conditions: (1) The chemical formula of the lithium-based crystalline oxide host material is Li x A m TM 1-y M y O 2±δ and / or Li x+α A m TM 1-α- y M y O 2±δ A represents a non-lithium alkali metal, TM represents a transition metal and / or a main group metal that constitutes the main framework of lithium-based basal oxide materials, and M represents a doping element. (2) The main material of the lithium-based layered oxide is lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium nickel manganese oxide, lithium-rich manganese-based layered oxide, lithium-rich nickel-rich layered oxide or Fe-containing layered oxide. (3) The crystalline phase of the lithium-based layered oxide host material includes one or more of O3, O2, T2, O6 and their distorted layered structures; (4) The chemical formula of the composite oxide reconstructed interface layer includes A′B′O 3±δ Li ρ A′ q B′O 3±δ A′2B′O 4±δ A′2B′2O 7±δ and A′2B′B″O 6±δ One or more of the following types of composite oxides; (5) The thickness of the composite oxide reconstructed interface layer is 0.3-500 nm; (6) The composite oxide reconstructed interface layer is formed by an external A′ source reacting in situ with the B′ site elements and / or B″ site elements near the surface of the lithium-based morphological oxide host material, or by simultaneously adding an external A′ source and a B′ source to control the interface phase composition. (7) In the functional coating layer, the solid electrolyte material is an oxide solid electrolyte and / or a polymer-inorganic composite solid electrolyte, wherein the inorganic phase in the polymer-inorganic composite solid electrolyte is a non-halide solid electrolyte; (8) In the functional coating layer, the compound containing polyanionic structural units includes at least one of the following: discrete oxygen-containing anions, condensed oxygen-containing anions, and oxygen-containing network structural units formed by at least one of the central atoms of P, B, Si, and S with O; (9) In the functional coating layer, the polyanionic structural unit in the compound containing the polyanionic structural unit includes orthophosphate (PO4). 3- pyrophosphate P2O7 4- BO3- orthoborate 3- SiO4 orthosilicate 4- and sulfate SO4 2- At least one of them; (10) In the functional coating layer, the inorganic glassy material is a lithium-containing glassy network material; (11) In the functional coating layer, the amorphous oxide is an amorphous inorganic oxide; (12) In the functional coating layer, the metal oxide includes at least one of γ-Al2O3, α-Al2O3, δ-Al2O3, θ-Al2O3, TiO2, ZrO2, Nb2O5, Ta2O5, MgO, ZnO, CeO2, SnO2, WO3, MoO3 and their doped or defect derivatives; (13) In the functional coating layer, the carbonaceous material includes at least one of disordered carbon, hard carbon, soft carbon, graphitized carbon, heteroatom-doped carbon and polymer-derived carbon; (14) In the functional coating layer, the polymer source corresponding to the heat-treated convertible organic polymer material before heat treatment includes one or more of the following: nitrile polymers, imide-containing polymers, fluorinated polymers, acrylate polymers, hydroxyl- or ether-containing polymers, nitrogen-containing heterocyclic polymers, aromatic thermosetting polymers, natural polymers and their derivatives.
4. The multiphase fast-transport layered cathode material as described in claim 3, characterized in that, The chemical formula of the lithium-based crystalline oxide host material satisfies one or more of the following conditions: (1) In the chemical formula, A includes one or more of Na, K, Rb and Cs; (2) In the chemical formula, the transition metal includes one or more of Co, Ni, Mn and Fe; (3) In the chemical formula, the main group metals include Al and / or Mg; (4) M in the chemical formula includes one or more of alkaline earth metals, transition metals, rare earth elements and p-block elements; (5) Said Li x A m TM 1-y M y O 2±δ Medium, 0.2≤x≤1.00; 0≤m≤0.30; 0≤y≤0.30; (6) Said Li x+α A m TM 1-α-y M y O 2±δ Medium, 0.2≤x≤1.00; 0<α<0.50; 0≤m≤0.3; 0≤y≤0.30; And / or, the composite oxide reconstructed interface layer satisfies one or more of the following conditions: (7) In the chemical formula, the element at the A′ position includes one or more of La, Ca, Sr, Ba, Ce, Pr, Nd, Gd, Y, Sm and Bi; (8) In the chemical formula, the B′ element and / or B″ element are metal elements near the surface of the lithium-based morphological oxide host material; (9) In the chemical formula, the molar amount of the element at the A′ site is 0.01%-15% of the total molar amount of the metal constituting the main framework in the lithium-based layered oxide host material; (10) The thickness of the composite oxide reconstructed interface layer is 1-100 nm; And / or, the functional overlay layer satisfies one or more of the following conditions: (11) The oxide solid electrolyte includes garnet-type Li7La3Zr2O 12 Garnet-type Li7La3Zr2O 12 Dopant, NASICON type Li 1+x1 Al x1 Ti 2-x1 (PO4)3, Li 1+x2 Al x2 Ge 2-x2 (PO4)3, perovskite-type Li 3x3 La 2 / 3-x3 At least one of TiO3 and LiPON; (12) The inorganic phase in the polymer-inorganic composite solid electrolyte is at least one of oxide solid electrolyte, phosphate solid electrolyte, borate solid electrolyte and silicate solid electrolyte; (13) The oxygen-containing network structure unit includes at least one of phosphorus-oxygen tetrahedral unit PO4, tricoordinated boron-oxygen unit BO3, tetracoordinated boron-oxygen unit BO4 and silicon-oxygen tetrahedral unit SiO4. (14) In the oxygen-containing network structural unit, adjacent structural units are connected by one or more bridging methods among P-O-P, B-O-B, Si-O-Si, P-O-B, P-O-Si, B-O-Si and S-O-B; (15) The inorganic glassy material includes at least one of lithium phosphorus oxy glassy material, lithium boron oxy glassy material, lithium boron phosphorus oxy glassy material, lithium silicon oxy glassy material, lithium silicon phosphorus oxy glassy material and lithium aluminum phosphorus oxy glassy material; (16) The amorphous oxide includes at least one of amorphous B2O3, amorphous SiO2, amorphous Al2O3, and amorphous ZrO2; (17) The heteroatoms in the heteroatom-doped carbon include at least one of N, B, P and S.
5. A method for preparing a multiphase fast-transport layered cathode material as described in any one of claims 1-4, characterized in that, Includes the following steps: Method 1: (1) The metal TM source, the non-lithium alkali metal A source and the doped element M source are dry-mixed and then heat-treated to obtain a layered oxide precursor; (2) The layered oxide precursor, lithium source and interface reconstruction element A′ source are dry-mixed and then heat-treated to obtain lithium-based layered oxide intermediate material; (3) The lithium-based layered oxide intermediate material is coated with a coating material source to obtain the multiphase fast transport layered cathode material; Method 2: (1) The metal TM source, the non-lithium alkali metal A source and the doped element M source are dry-mixed and then heat-treated to obtain a layered oxide precursor; (2) The mixture of the layered oxide precursor and the lithium source is subjected to topological exchange to obtain a lithium-based layered oxide material; (3) The lithium-based morphological oxide material, lithium source and interface reconstruction element A′ source are dry-mixed and then heat-treated to obtain lithium-based morphological oxide intermediate material; (4) The lithium-based layered oxide intermediate material is coated with a coating material source to obtain the multiphase fast transport layered cathode material; When the main material of the multiphase fast transport layered cathode material is a metastable phase material, method one is used; when the main material of the multiphase fast transport layered cathode material is a stable phase material, either method one or method two is used. The TM element in the metal TM source includes transition metals and / or main group metals that constitute the main framework of the layered oxide precursor; the M element in the doping element M source includes one or more of alkaline earth metals, transition metals, rare earth elements, and p-block elements; the A′ element in the interface reconstruction element A′ source includes metal elements capable of forming a composite oxide interface structure with metal elements near the surface of the host material; the coating material source includes at least one of solid electrolyte source, polyanionic compound source, inorganic glassy material source, amorphous oxide source, metal oxide source, carbon source, and polymer source.
6. The method for preparing the multiphase fast-transport layered cathode material as described in claim 5, characterized in that, The preparation method satisfies one or more of the following conditions: (1) Among the TM elements in the metal TM source, the transition metal includes one or more of Co, Ni, Mn and Fe; (2) Among the TM elements in the metal TM source, the main group metals include Al and / or Mg; (3) The metal TM source is an oxide of metal TM and / or a salt that can decompose to form the corresponding metal TM oxide during heat treatment; (4) The A element in the non-lithium alkali metal A source includes one or more of Na, K, Rb and Cs; (5) The non-lithium alkali metal A source is a salt of A and / or a base of A; (6) The molar ratio of element A in the non-lithium alkali metal A source to the total molar amount of element TM in the metal TM oxide source and element M in the doped element M source is (0.1-2.0):1; (7) The M element in the doping element M source includes one or more of Ti, Zr, Nb, Ta, W, Mo, Sb and Sn; (8) The dopant element M is sourced from an oxide of M; (9) The molar ratio of element M in the doped element M source to the total molar amount of element TM in the metal TM oxide source and element M in the doped element M source is 0.05%-5%; (10) In step (1) of method one and / or step (1) of method two, a lithium source is added before the dry mixing; the molar ratio of element A in the non-lithium alkali metal A source to element Li in the lithium source is 1:(0-1). (11) In step (2) of method one and / or step (2) of method two, the lithium source is one or more of LiNO3, LiCl, LiBr, LiI, LiOH, Li2CO3, Li2O, LiCH3COO and Li2SO4; (12) In step (2) of method one and / or step (2) of method two, the molar ratio of Li element in the lithium source to A element in the non-lithium alkali metal A source in the layered oxide precursor is (1-30):1; (13) In step (2) of method one and / or step (3) of method two, the A′ element in the A′ source includes one or more of La, Ca, Sr, Ba, Ce, Pr, Nd, Gd and Y; (14) In step (2) of method one and / or step (3) of method two, the A′ source may include one or more of the following: oxides, hydroxides, carbonates, nitrates, hydrochlorides, acetates, and precursors that can be thermally decomposed to form the corresponding oxides; (15) In step (2) of method one and / or step (3) of method two, a B′ source and / or a B″ source are added before the dry mixing; the B′ element in the B′ source and / or the B″ element in the B″ source includes one or more of Ti, Zr, Hf, Nb, Ta, W, Mo, Sn, Co, Ni, Mn, Fe, Cr, V, Ga, In and Al; (16) In step (2) of method one, the ratio of the total molar amount of the A′ element in the A′ source to the total molar amount of the non-alkali metal element in the layered oxide precursor is 0.01%-15%; (17) In step (3) of method two, the ratio of the total molar amount of the A′ element in the A′ source to the total molar amount of the non-alkali metal elements in the lithium-based layered oxide material is 0.01%-15%; (18) In step (3) of method two, the molar percentage of Li element in the lithium source to that of the lithium-based layered oxide material is 1%-30%; (19) In step (3) of method one and / or step (4) of method two, the solid electrolyte source is an oxide solid electrolyte and / or a polymer-inorganic composite solid electrolyte, wherein the inorganic phase in the polymer-inorganic composite solid electrolyte is a non-halide solid electrolyte; (20) In step (3) of method one and / or step (4) of method two, the polyanionic compound source includes one or more of phosphoric acid, polyphosphoric acid, phosphate, boric acid, borates, silicates and sulfates; (21) In step (3) of method one and / or step (4) of method two, the inorganic glassy material source includes at least one of phosphorus source, boron source, silicon source and aluminum source and a mixture of lithium source; (22) In step (3) of method one and / or step (4) of method two, the amorphous oxide source is an amorphous inorganic oxide; (23) In step (3) of method one and / or step (4) of method two, the metal oxide source includes at least one of γ-Al2O3, α-Al2O3, δ-Al2O3, θ-Al2O3, TiO2, ZrO2, Nb2O5, Ta2O5, MgO, ZnO, CeO2, SnO2, WO3, MoO3 and their doped or defective derivatives; (24) In step (3) of method one and / or step (4) of method two, the carbon source includes acetylene black, Ketjen black, furnace black, graphite, expanded graphite, graphene, graphene oxide, reduced graphene oxide, carbon nanotubes, carbon nanofibers, hard carbon, soft carbon, disordered carbon, carbon quantum dots, and one or more of carbon doped with at least one heteroatom of N, B, P and S. (25) In step (3) of method one and / or step (4) of method two, the polymer source includes one or more of the following: nitrile polymers, imide-containing polymers, fluoropolymers, acrylate polymers, polymers containing hydroxyl or ether bonds, nitrogen-containing heterocyclic polymers, aromatic thermosetting polymers, natural polymers and their derivatives. (26) In step (3) of method one and / or step (4) of method two, the mass of the coating material source accounts for 0.1%-10% of the mass of the lithium-based layered oxide intermediate material; (27) In step (3) of method one and / or step (4) of method two, the coating treatment is one or more of liquid phase coating, dry coating and vapor phase deposition coating.
7. The method for preparing the multiphase fast-transport layered cathode material as described in claim 5, characterized in that, The preparation method satisfies one or more of the following conditions: (1) The dry mixing method is grinding, planetary ball milling, vibratory ball milling, mechanical fusion, airflow mixing, high-speed shear mixing, jet mixing or roller pressing mixing; (2) In step (1) of method one and / or step (1) of method two, the temperature of the heat treatment is 450-1100℃; (3) In step (1) of method one and / or step (1) of method two, the heat treatment time is 0.2-48h; (4) In method one, in step (2), the temperature of the heat treatment is 200-400℃; (5) In method one, in step (2), the heat treatment time is 10 min to 8 h; (6) In Method 2, in step (2), the topological exchange adopts molten salt exchange, solid-phase exchange or solid-liquid synergistic exchange; (7) In method two, in step (3), the temperature of the heat treatment is 400-900℃; (8) In method two, in step (3), the heat treatment time is 1-12 hours; (9) In step (3) of method one and / or step (4) of method two, when the coating treatment is liquid phase coating, the liquid phase coating includes the following process: adding the lithium-based morphological oxide intermediate material to a dispersion containing a coating material source to obtain a mixture, and then subjecting the mixture to solvent evaporation and heat treatment.
8. A multiphase fast-transport layered cathode material prepared by the preparation method of any one of claims 5-7.
9. A battery, characterized in that, It includes a positive electrode, a negative electrode, and an electrolyte, wherein the positive electrode active layer on the positive electrode includes a multiphase fast transport layered positive electrode material as described in any one of claims 1-4 and 8.
10. The application of a multiphase fast-transport layered cathode material as described in any one of claims 1-4 and 8 in a battery.
Citation Information
Patent Citations
Secondary battery and electrode material for same
CN108539151A
Lithium battery positive electrode material interface boronizing method and solid-state lithium battery
CN120464973A